Resilience–oriented mitigation strategies for catastrophic tunnel collapse induced by deep excavation disturbance - Omer Javaid; Muhammad Irslan Khalid; Debo Zhao; Rana Muhammad Asad Khan; Xiaohua Bao; Xiangsheng Chen (Tunnelling and Underground Space Technology, 2026)

Multifunctional bioactive films based on carboxymethyl cellulose/sodium alginate incorporated with DES-lignin-stabilized ginger oil nanoemulsion and gallic acid for enhanced shelf-life of cherry tomatoes - Asad Mukhtar; Muhammad Abdur Rehman Shah; Haoxin Li; Xiaojie Yu; Albert Abugri; Allah Rakha; Rana Abdul Basit; Areej Munir; Li Chen; Hua Yang; Cunshan Zhou (Food Hydrocolloids, 2026)

Clinico-genetic heterogeneity in Pakistani families affected with muscular dystrophies - Riaz Ahmad; Muhammad Almas Hashmi; Asad Ullah; Ubaid Ur Rehman; Muhammad Naeem; Henry Houlden (Molecular Biology Reports, 2026)
Background Muscular dystrophies are a group of inherited neuromuscular disorders characterized by degenerative and progressive muscle weakness. Duchenne muscular dystrophy (DMD), Becker muscular dystrophy (BMD) and merosin-deficient congenital muscular dystrophy type 1 (MDC1A) are frequent forms caused by DMD (NM_004006.3) and LAMA2 (NM_000426.4) mutations, respectively. Methods and results Our study used whole exome sequencing to explore the molecular genetics of muscular dystrophies in six unrelated Pakistani families. We found four novel variants in the LAMA2 ; c.7470_7473del; p.(Lys2490AsnfsTer56) in family A, c.7807del; p.(Ala2603HisfsTer4) in family C, c.8651T > C; p.(Met2884Thr) in family D and c.4127T > A; p.(Leu1376Ter) in family E associated with MDC1A in these families. Furthermore, two already cited DMD variants were identified: c.10,801 C > T; p.(Gln872Ter) in family B and hemizygous genomic deletion in DMD (NM_004006.3):g.32438241_32809611del (corresponding to deletion of exons 7–29; GRCh38), which was identified (in family F) associated with BMD and DMD, respectively. Conclusions We present the first report of MDC1A-associated phenotypes caused by the LAMA2 gene in the Pakistani population, while DMD -related cases have already been documented in the literature and public databases. Clinical and molecular diagnosis of these six affected families will be valuable in therapeutic interventions and prenatal diagnosis of neuromuscular dystrophies in the familial and Pakistani populations. Our study emphasizes the effectiveness of next generation sequencing technology over traditional diagnostic methods such as muscle biopsies.

Mechanistic insights into the dynamics of plasma membrane repair in cancer - Yufeng Huang; Asad Ullah; Muhammad Muddassir Ali (Molecular Biology Reports, 2026)

Precision nanoparticles for plant thermotolerance: From molecular mechanisms to scalable agriculture - Muhammad Azeem Ashraf; Muhammad Ateeq; Muhammad Amjad; Qingfeng Dong; Hao Ren; Asad Shehzaib; Wang Xue; Liang Chen; Yin-Gang Hu (Plant Science, 2026)

Mitigation of aflatoxin B1-induced toxicopathology and immunosuppression in broilers using a multimodal antioxidant formulation - Muhammad Asad Ali; Muhammad Abdullah Arshad; Aisha Khatoon; Muhammad Kashif Saleemi; Shafia Tehseen Gul; Muhammad Umar Ijaz; Sadaf Faiz; Aneela Amin (Mycotoxin Research, 2026)

Streptomyces griseoincarnatus AR2 from the cold desert as a biofactory for secondary metabolites with multifaceted bioactivities, confirmed by in vitro and in silico approaches - Arisha Rameen Bhatti; Noor Hassan; Hazrat Ali; Noor ul Huda; Abdul Tawab; Saba Khan; Ambreen Latif; Asad Ali; Waseem Abbas; Iqra Latif Ghuman; Mohsin Khan; Aiman Umar; et al. (Archives of Microbiology, 2026)

Decoupling methanogenesis to boost hydrogen production via microalgae–wastewater co-digestion in a continuous stirred reactor - Muhammad Asad Javed; Ashraf Aly Hassan (Fuel, 2026)

Engineering of novel N-TiO2/P-doped graphene oxide nanocomposite: Mechanistic insights into the photocatalytic removal of benzophenone-3 and H2 production - Wisal Ahmad; Suyeon Jeon; Roman Shah; Dilaram Khan; Syed Izaz Ali Shah; Muhammad Anwar; Raed Al-Juboori; Asad Ali; Noor S. Shah; Javed Ali Khan; Changseok Han (Chemical Engineering Journal, 2026)

Development and Characterization of Exosomes Mediated Transdermal Gel for Enhanced Delivery of Hydroxyurea - Wajeeha Khalid; Rabia Gul; Muhammad Sarfraz; Hamid Bashir; Nadeem Ahmad; Nayab Tahir; Aneela Javed; Muhammad Asad; Ahsan Ibrahim; Aamra Imtiaz; Imran Nazir; Muhammad Imran Amirzada (Journal of Pharmaceutical Innovation, 2026)

Editorial Expression of Concern: Silicon inhibits cadmium uptake by regulating the genes associated with the lignin biosynthetic pathway and plant hormone signal transduction in maize plants - Tariq Shah; Zeeshan Khan; Shah Rukh Khan; Ayesha Imran; Muhammad Asad; Ajaz Ahmad; Parvaiz Ahmad (Environmental Science and Pollution Research, 2026)

CRISPR-based gene editing for antimicrobial resistance control in human medicine - Abdullah Afzal Alvi; Muzzamil Hussain; Sadia Noureen; Zahid Abbas Malik; Sidra Zahoor; Areej Jamil; Muhammad Ali Mohsin; Asad Azeem; Haseeb Javaid; Zeshan Hassan (Archives of Microbiology, 2026)

Climate Change Intensifies Cropland Drought Exposure in the Indus River Basin During the 21st Century - Muhammad Asad Hussain; Barira Haider; Muhammad Waseem; Buda Su; Muhammad Akbar; Jinlong Huang; Jian Zhou; Tong Jiang (International Journal of Climatology, 2026)
Drought poses a significant threat to agriculture in the transboundary Indus River Basin (IRB), which supports over 300 million people through direct and indirect dependence on agriculture. With limited cropland and growing climatic stress, the basin faces an increasing risk to food security. Yet, comprehensive assessments of cropland exposure to drought under a changing climate and socioeconomic conditions remain lacking. This study evaluates present and future cropland exposure to drought across the IRB using cropland data from the Land‐Use Harmonisation dataset (LUH2) and bias‐corrected output from seven CMIP6 global climate models, validated against ERA5 reanalysis data. We examined a baseline period (1995–2014) and three future time slices (2021–2040, 2041–2060 and 2081–2100) under seven Shared Socioeconomic Pathways (SSP1‐1.9 to SSP5‐8.5). Drought characteristics are quantified using the Standard Precipitation Evapotranspiration Index (SPEI) combined with run theory, incorporating CO 2 emissions. Results indicate that drought frequency is increasing in the future across the emission scenarios relative to the baseline. Cropland exposure displays pronounced spatial heterogeneity and a clear dynamic evolution over time, with the highest concentrations in the central IRB, particularly the Indo‐Pak Punjab and riparian corridors. By 2081–2100, annual cumulative exposed cropland area expands from 1875.3 to 2886.5 km 2 , representing an increase of 71.8%–88.1% relative to the baseline. Furthermore, attribution analysis shows that climate change dominates the increase in exposure through 2060, whereas cropland emerges as the primary driver by 2081–2100. These findings underscore the need for dual‐track drought risk‐management: climate‐focused adaptation for near‐term and integrated land‐use planning for long‐term resilience to safeguard food security in the IRB.

Exploring Carissa spinarum as a therapeutic candidate: metabolite profiling and antimicrobial evaluation - Laiba Ali; Shahid Nawaz; Sikandar Ali; Asad Ur Rehman; Iram Liaqat; Shaukat Ali; Muhammad Nauman Aftab (Natural Product Research, 2026)

Retraction notice to “Responses of microbial communities in rhizocompartments of king grass to phytoremediation of cadmium-contaminated soil” [Sci. Total Environ. 904 (2023) 167226] - Muhammad Khalid; Xinxin Liu; Saeed ur Rahman; Asad Rehman; Chang Zhao; Xiaoxiao Li; Bian Yucheng; Nan Hui (Science of The Total Environment, 2026)

Mapping the spatial heterogeneity of nitrogen species in road dust through integrated multi-source remote sensing and interpretable machine learning - Muhammad Nabil Ashraf; Suiliang Huang; Asad Basheer (Environmental Research, 2026)

MOF-based composite catalysts for CO2 reduction: Recent advances and perspectives - Asad Ur Rehman; Syed Shoaib Ahmad Shah; Sami Ullah; Arooj Fatima; Ibrahim A. Shaaban; Muhammad Sufyan Javed; Awais Ahmad; Muhammad Altaf Nazir (Environmental Research, 2026)

Geostatistical and PMF-based source apportionment of heavy metal contamination in the groundwater of Faisalabad, Pakistan: water quality and health risk assessment - Muhammad Hassan Bashir; Asad Hussain; Muhammad Tahir Shehzad; Amna Zulfqar (Stochastic Environmental Research and Risk Assessment, 2026)

Integrating geostatistics and landsat-8 OLI imagery for regional-scale spatial mapping and remote assessment of soil and foliar nitrogen status in citrus agroecosystem - Humair Ahmed; Muhammad Asad Hameed; Nabeeha Javed; Munazza Yousra; Maria Niaz; Bushra Baloch; Muydinjon Muminov; Sarah Abdul Razak; Shaimaa A. M. Abdelmohsen; Muhammad Tahir Naseem (Environmental Geochemistry and Health, 2026)

CRISPR-Cas systems for enhancing chilling tolerance in rice: recent advances and future prospects - Muhammad Sikandar Zaman; Asad Azeem; Ayesha Nouman; Abdullah Khalid; Saira Ghafoor; Muhammad Zia Ul Haq; Muhammad Talha Aslam; Hossam S. El-Beltagi (Biologia Futura, 2026)

Petrogenesis and tectonic implications of the Late Palaeozoic Koga alkaline–carbonatite complex, NW Pakistan: insights from U–Pb geochronology, geochemistry, and Sr–Nd–C–O isotopes - Asad Khan; Zaheen Ullah; Huan Li; Shah Faisal; Delores M. Robinson; Muhammad Farhan; Nasir Ahmad (International Geology Review, 2026)

The AI revolution in sustainable food processing: From process optimization to a circular bioeconomy - Asad A. Zaidi; Aisha Jilani; Muhammad Asif; Asim Laeeq Khan; Sohaib Z. Khan (Food and Bioproducts Processing, 2026)

Assessment of Fine Particulate Matter (PM2.5) Induced Cyto-Genotoxicity in a Highly Polluted Urban Environment: Evidence from Lahore, Pakistan - Meerub Shazad; Muhammad Muddassir Ali; Syed Aziz ur Rehman; Maryam Javed; Jabir Hussain Syed; Asad Ullah (Water, Air, & Soil Pollution, 2026)

Light Duration Dictates Photomorphogenic and Adaptive Responses to Post-Anthesis Drought in Maize: Stomatal, Biochemical and Genetic Mechanisms - Ahmed Mukhtar; Shaista Jabeen; Muhammad Asad Naseer; Muhammad Tauseef Jaffar; Muhammad Shoaib Asad; Xiaoli Chen; Xiaolong Ren (Journal of Plant Growth Regulation, 2026)

Influence of thermal pretreatment on characteristic and anaerobic digestion of Sunflower meal - Asad Ayub Rajput; Zeshan; Muhammad Raheel Bawani; Saleem Raza Chalgri (Bioresource Technology Reports, 2026)

Integrated facies analysis and diagenetic impact on carbonate reservoirs: a case study from Jurassic shallow marine carbonate platform, NW Himalayas, Pakistan - Ihsan Ullah; Muhammad Jamil; Hamad ur Rahim; Imran Khan; Wahid Abbas; Asad Ali; Mohib Ur Rehman (Carbonates and Evaporites, 2026)

Nutritional and phytochemical profiling of Solanum melongena L. root extract using LC-ESI-MS/MS; In-silico and biological evaluation - Asad Saleem Sial; Muhammad Mohtasheemul-Hasan; Khizar Abbas; Rizwana Manzoor; Usman Javaid; Syed Zia Ul Hasnain; Adnan Amin (South African Journal of Botany, 2026)

Tracing subduction initiation in the Neo-Tethyan Realm: Geochemical and isotopic signatures in lherzolites of the Sapat Complex, Northern Pakistan - Zaheen Ullah; Qigui Mao; Asad Khan; Meng Zhang; Dunfeng Xiang; Wang Hao; Tehseen Zafar; Wenjiao Xiao; Adnan Khan; Muhammad Ibrar (Lithos, 2026)

Bacillus subtilis enhances maize yield by restricting cadmium translocation and modulating ion homeostasis - Haseeb Ahmad; Jiu Yang Mao; Rayyan Khan; Muhammad Ali Shah; Kashif Khan; Muhammad Asad Naseer; Shahid Ali; Rida Rashid; Rui He; Xun Bo Zhou (Journal of Environmental Sciences, 2026)

Synergistic Degradation and Cytotoxicity Mitigation of Meloxicam Using UV/Perovskite/H₂O₂ and Gamma/H₂O₂: A Comparative Study - Muhammad Asad Khan; Mohamed A. Habib; Muhammad Imran Kanjal; Majid Muneer; Muhammad Asghar Jamal; Tanveer Hussain Bokhari; Usman Irshad; Ahmed B. M. Ibrahim (Water, Air, & Soil Pollution, 2026)

Spatial Distribution and Risk Assessment of Heavy Metal Pollution at an Abandoned Smelting Site in Guangxi Province of China - Bodong Xiong; Lizhu Hou; Wajahat Waseem; Weihua Cui; Muhammad Asad ghafoor (Environmental Management, 2026)

The Knowledge Compliance Paradox in Irrigation Governance: Evidence From the Bengawan Solo Basin, Indonesia - Agus Hari Wahyudi; Ratri Werdiningtyas; Rintis Hadiani; Sholihin Asad; Solichin; Muhammad Miftahur Rozaq (Irrigation and Drainage, 2026)
Participatory changes have not solved farmer noncompliance with irrigation restrictions, proving that technical knowledge alone is insufficient for good governance. The knowledge compliance paradox in irrigation governance examines how farmers' views of the system's technical components might strengthen or diminish collective compliance with water management. This research employs data gathered from 187 farmers across 49 irrigation districts within the Bengawan Solo Basin in Indonesia. This study utilises partial least squares structural equation modelling (PLS‐SEM) to analyse the interactions between knowledge, institutional trust, social capital and compliance in relation to adherence to cropping and water quota regulations. The research findings indicate that knowledge of cropping rules negatively impacts compliance ( β = 0.23, p β = 0.82, p β = 0.11, p

Navigating mobility in later life: How vehicle access and community context shape travel behaviour among older adults - Muhammad Adeel; Asad J. Khattak; Moetasim Ashfaq (Travel Behaviour and Society, 2026)

Tracking tectonic evolution from ridge to trench: Geodynamic constraints from the Chitral complex, Neo-Tethyan domain (NW Pakistan) - Zaheen Ullah; Qigui Mao; Asad Khan; Wenjiao Xiao; Meng Zhang; Hadi Shafaii Moghadam; Muhammad Farhan; Songjian Ao; Tehseen Zafar; Wang Hao (Lithos, 2026)

Photo-activated defect engineering unlocks high-performance proton transport in garnet electrolytes - Bushra Bibi; Atif Nazar; Muhammad Yousaf; Tanveer Farid; Rizwan Raza; Syed Asad Abbas Bukhari; Muhammad Faisal Anawar; Kashif Nazar; Hafsa Mansha; Yuzheng Lu; Bin Zhu (Chemical Engineering Journal, 2026)

Modelling urban roads particulate matter and airborne traffic-related metals exposure: AERMOD-Support vector machine hybrid framework for Monte Carlo health risk assessment - Muhammad Hassan Bashir; Asad Abbas; Hamaad Raza Ahmad; Muhammad Tahir Shehzad (Atmospheric Pollution Research, 2026)

Genetic and epigenetic mechanisms underlying cadmium (Cd) stress responses in soybean cultivars - Shahid Ali; Ya Huang; Rayan Khan; Kashif Khan; Yu Xin Chi; Muhammad Ali Shah; Muhammad Asad Naseer; Haseeb Ahmad; Wen Jie Chen; Xun Bo Zhou (Plant Cell Reports, 2026)

Retraction Note: Optimizing callogenesis in five potential medicinal herbs for the bioactive constituents: a sustainable approach to pharmaceutical production - Muhammad Wasim Haider; Muhammad Nafees; Maryyam Bint-e-Tariq; Umar Farooq; Tanveer Hussain; Taki Demir; Asad Masood; Muhammad Samsam Raza; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Ozhan Simsek; Temoor Ahmed; et al. (Genetic Resources and Crop Evolution, 2026)

Omics-driven soil bioremediation of emerging contaminants: Integrating sensors, digital twins, and microbial biotechnology - Asad Shah; Mohammad Nauman Khan; Waqar Ali; Muhammad Numan Khan; Hidayat Ullah; Zahra Barati; Adil Farooq Lodhi; Lixiao Nie (Applied Soil Ecology, 2026)

Carboxymethyl cellulose/sodium alginate composite films encapsulated with turmeric essential oil-in-water nanoemulsion and gallic acid for grapes preservation - Muhammad Abdur Rehman Shah; Rahmat Ali Khan; Hidayat Ullah Khan; Obaid Ur Rehman; Sadaf-Ilyas Kayani; Liaqat Zeb; Khalid Ali Khan; Asad Mukhtar; Shuhao Huo (Food Chemistry, 2026)

Synergistic effect of Clupea harengus by-product hydrolysates and kappa carrageenan mixture on oxidation prompted structural alterations in Clupea harengus proteins during frozen temperature variations - Noman Walayat; Piotr Kulawik; Asad Nawaz; Isam A. Mohamed Ahmed; Muhammad Faisal Manzoor; Zhucheng Su; Ran Wei (Food Hydrocolloids, 2026)

Advances in green food processing technologies: Enhancing efficiency, safety, and sustainability - Asad Nawaz; Sana Irshad; Xiaofang Luo; Noman Walayat; Putri Widyanti Harlina; Zuodong Qin; Muhammad Afzaal; Fakhar Islam (Food Control, 2026)

Retraction notice to “Comparative study of ZIF-8-materials for removal of hazardous compounds using physio-chemical remediation techniques” [Environ. Res. 220 (2023) 115168] - Bazla Sarwar; Asad Ullah Khan; Muhammad Aslam; Awais Bokhari; Muhammad Mubashir; Asma A. Alothman; Mohamed Ouladsmane; Samar A. Aldossari; Wai Siong Chai; Kuan Shiong Khoo (Environmental Research, 2026)

Detection and serotyping of bluetongue viruses in Khyber Pakhtunkhwa Province, Pakistan - Muhammad Ishaq; Syed M. Jamal; Syed Asad Ali Shah; Hanif Ur Rahman; Alessandra Leone; Liana Teodori; Maura Pisciella; Ottavio Portanti; Cesare Cammà; Valentina Curini; Maurilia Marcacci; Barbara Secondini; et al. (Tropical Animal Health and Production, 2026)

Hematological, Histological, and NMR Analysis of Meat Quality and Growth Performance of Broilers Fed with Probiotics Bacillus licheniformis-Supplemented Poultry Feed - Basit Ali Khan; Sundas Sharif; Amna Mehdi; Iram Liaqat; Sikander Ali; Asad-ur-Rehman; Liangcai Peng; Sohail Afzal; Muhammad Nauman Aftab (Probiotics and Antimicrobial Proteins, 2026)

Trichoderma Enhance Soil Properties in Fusarium Infested Soil and Increase Mineral Nutrients of Chickpea Grains: Findings from Field Experiments - Safeer Akbar Chohan; Muhammad Akbar; Muhammad Asad Farooq; Nasim Ahmad Yasin; Umer Iqbal; Tayyaba Khalil (Journal of Soil Science and Plant Nutrition, 2026)

Molecular Detection and Phylogenetic Characterization of Avian Infectious Bronchitis Virus (IBV) in Vaccinated Commercial Chicken Flocks Experiencing Outbreaks in Faisalabad, Pakistan - Muhammad Mubeen Ahmad; Muhammad Wasif Gulzar; Muhammad Wasif Azeem; Muhammad Musa Mubashar; Rida Fatima; Muhammad Tayyab Naveed; Muhammad Taha; Sana Riaz; Asad Javed; Mudasser Habib; Rizwan Aslam (Archives of Virology, 2026)

MOF/Graphene interfaces in catalytic water splitting: Recent breakthroughs and future outlook - Asad Ur Rehman; Muhammad Asghar; Abdul Rauf; Tayyaba Najam; Ibrahim A. Shaaban; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Fuel, 2026)

Deep eutectic solvent-extracted lignin as a natural emulsifier for ultrasound-assisted ginger oil nanoemulsions with enhanced antioxidant and antimicrobial activities - Asad Mukhtar; Muhammad Abdur Rehman Shah; Yang Wang; Chenhui Hua; Haoxin Li; Jiakang Liang; Ziwei Zhu; Md Razaul Karim; Yasyn Boutayeb; Xue Wang; Li Chen; Cunshan Zhou (Food Chemistry, 2026)

Antibiotic resistance dissemination in soil ecosystems: deep understanding for effective management and global health protection - Lu Li; Juexi Li; Saeed ur Rahman; Asad Rehman; Muhammad Khalid (BioMetals, 2026)

Sodium carbonate and sodium chloride as elicitors of secondary metabolite production in callus cultures of Fagonia indica - Muhammad Uzair Javed; Muhammad Asad Ullah; Tehreem Mahmood; Taimoor Khan; Iva Viehmannova; Anmol Akbar; Yasir Khan; Tariq Khan; Bilal Haider Abbasi; Christophe Hano; Nathalie Giglioli-Guivarc’h (Plant Biosystems, 2026)

Laccase purification and azo dye decolorization potential of Sparassis latifolia - Abdul Rehman Niazi; Tehreem Fatima; Aneeqa Ghafoor; Munir Ahmad; Muhammad Asad Ghafoor; Abdulaziz Bentalib; Muhammad Bilawal Junaid; Imran Haider (Natural Product Research, 2026)

Bacterial community in household municipal solid waste and bioaerosols released: Implications to health risks - Boning Kong; Shuang Li; Muhammad Asad; Yanqing Liu; Yuyang Long; Yan Zhao; Xia Huang; Ming Zhao; Wenjing Lu (Journal of Environmental Management, 2026)

Balancing efficacy and resistance: oils vs. synthetic acaricides in the control of Panonychus citri - Muhammad Asif Qayyoum; Syed Husne Mobarak; Bilal Saeed Khan; Rehan Inayat; Asad Nawab; Tian-Ci Yi (Experimental and Applied Acarology, 2026)

Climate-responsive cropland dynamics in Indus Basin: A comprehensive SDM assessment with intra-seasonal variability - Fatima Ilyas; Muhammad Azmat; Swera Javed; Shakil Ahmad; Muhammad Arshad; Muhammad Usman Rashid; Saeed Ahmad Asad (Science of The Total Environment, 2025)

From genes to fields: Genetic determinants and tillage practices shaping cereal root systems for sustainable productivity - Asad Azeem; Sami Ul-Allah; Sana Khan; Muhammad Zia Ul Haq; Muhammad Sikandar Zaman; Syed Ali Murtaza Gallani (Rhizosphere, 2025)

Recent progress of metallic nanomaterials in energy, biomedical and environment sector - Kinza Maqsood; Sami Ullah; Asad ur Rehman; Hafsa Bashir; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Next Research, 2025)

Leveraging green roof technology: Stakeholder analysis of sustainable urban landscape in the developing regions of South Asia - Mehak Shehzad; Adnan Younis; Sabir Aziz; Muhammad Khizar; Noor ul Ain; Muhammad Asad Shabbir (Land Use Policy, 2025)

Temporal changes in soil dissimilarity are driven by synergistic effects of tree types and geographical distance in city parks - Saeed ur Rahman; Yucheng Bian; Xinxin Liu; Chang Zhao; Peiyuan Wang; Muhammad Khalid; Asad Rehman; Junfeng Cao; Noel Bruguera Amarán; Nan Hui (Landscape and Urban Planning, 2025)

Genotoxic and oxidative stress assessment of heavy metal contaminated soil and water in human blood and bovine milk samples from the different industrial zones of Punjab, Pakistan - Muhammad Muddassir Ali; Furqan Awan; Muhammad Usman Jamil; Muhammad Ijaz; Asad Ullah; Wasim Shehzad (Journal of Trace Elements in Medicine and Biology, 2025)

Metal organic frameworks derived novel metal sulfide (KCoZnS) nanosheet as an efficient collector for cesium ions - Muhammad Ikram; Hongyan Liu; Iltaf Muhammad; Qirui Wang; Shahzad Afzal; Masood Ul Hasan Israr; Asad Ali; Yongquan Zhou (Journal of Environmental Chemical Engineering, 2025)

Incidence and Molecular Characterization of Tobacco Rattle Virus (TRV) in Azad Jammu and Kashmir-Northeast of Pakistan - Nayla Haneef; Muhammad Arif; Asad Ali; Muhammad Tariq Khan (Potato Research, 2025)

Microplastics in soil–plant systems: impacts on soil health, plant toxicity, and multiomics insights - Muhammad Ahsan Farooq; Fakhir Hannan; Hui-Xi Zou; Weijun Zhou; Dong-Sheng Zhao; Ahsan Ayyaz; Muhammad Asad Ullah Asad; Rehan Ahmad; Xiufeng Yan (Plant Cell Reports, 2025)

A combination of cry (Cry2Ab) and plant lectin (PTA) genes confers resistance against major sucking and chewing insect pests of cotton - Syed Najeebullah; Boaz Negin; Rubab Zahra Naqvi; Shaheen Asad; Zahid Mukhtar; Georg Jander; Muhammad Asif (Molecular Biology Reports, 2025)

Overexpression of rice High-affinity Potassium Transporter gene OsHKT1;5 improves salinity and drought tolerance in Arabidopsis - Mohammad Asad Ullah; Muhammad-Redha Abdullah-Zawawi; Izreen Izzati Razalli; Noor Liyana Sukiran; Md. Imtiaz Uddin; Zamri Zainal (Molecular Biology Reports, 2025)

Microfacies analysis and depositional environment of Eocene Chorgali formation at Khanpur Dam Road Section, Hazara Basin, Pakistan - Bilal Shah; Syed Mamoon Siyar; Salman Khurshid; Dicky Muslim; Raden Irvan Sophian; Zahid Ullah; Abdul Wahid Asykarulloh; Asad Muhammad; Syed Muhammad; Wasim Sajjad (Carbonates and Evaporites, 2025)

Deciphering the role of non-covalent interactions in CO2 Capture: A DFT and COSMO-RS study of amino acid-based ionic liquids - Hira Karim; Sabahat Sardar; Suhan Prasantha Panditharatne; Asad Mumtaz; Muhammad Arfan; Azhar Mahmood; Jean-Marc Leveque; Syed Farooq Adil; Mohammad Rafe Hatshan; Mujeeb Khan (Journal of Environmental Management, 2025)

Photo-activated proton-incorporation into Nd-aluminum for superionic conductors - Atif Nazar; Bushra Bibi; Sajid Rauf; Rizwan Raza; Muhammad Farrukh Sarfraz; Muhammad Khalid; Muhammad Faisal Anwar; Muhammad Ahsan Masood; Kashif Nazar; Syed Asad Abbas Bukhari; Khuloud A. Alibrahim; Bin Zhu; et al. (Chemical Engineering Journal, 2025)

Biofunctional and ecotoxicological assessment of Rosa indica derived nitrogen-doped Carbon Dots: A new frontier for sustainable nanomaterials - Hubza Ruatt Khan; Humaira Yasmeen; Muhammad Asad Tahir; Asna Fatima Kiani; Iqra Munir; Unzish Qamar; Sara Janiad; Saher Mahmood (Biocatalysis and Agricultural Biotechnology, 2025)

Estimation of genome-wide patterns of homozygosity, heterozygosity and inbreeding in crossbred dairy cattle population in Pakistan - Fakhar Un Nisa; Muhammad Usman; Asad Ali; Muhammad Basil Ali; Haiba Kaul; Muhammad Asif; Raphael Mrode; Zahid Mukhtar (Tropical Animal Health and Production, 2025)

Coupling no-tillage with bio-organic fertilizer strategies to regulate soil quality and microbial communities, without compromising crop yield under rainfed conditions on the Loess Plateau, China - Xiaoling Wang; Qingxuan Yang; Muhammad Shoaib Asad; Zinan Yan; Xiaoli Chen; Xining Zhao; Enke Liu; Zhikuan Jia; Kadambot H. M. Siddique; Xiaolong Ren (Plant and Soil, 2025)

Potential of Organic Amendments as a Sustainable Strategy to Enhance Rice Yield by Improving Nutrient Use Efficiency and Physiological Performance in Alkaline Soil - Muhammad Ahmed; Muhammad Tauseef Jaffar; Zulfiqar Ahmad; Muhammad Naveed; Syed Ayyaz Javed; Muhammad Shoaib Asad; Ali Raza; Awais Shakoor; Jianguo Zhang (Journal of Plant Growth Regulation, 2025)

Retraction notice to “Synergistic effect of silicon and arbuscular mycorrhizal fungi reduces cadmium accumulation by regulating hormonal transduction and lignin accumulation in maize” [Chemosphere 346, January 2024, 140507] - ShahRukh Khan; Zubair Ahmad; Zeeshan Khan; Umair Khan; Muhammad Asad; Tariq Shah (Chemosphere, 2025)

Retraction notice to “Strigolactone decreases cadmium concentrations by regulating cadmium localization and glyoxalase defense system: Effects on nodules organic acids and soybean yield” [Chemosphere 335, September 2023, 139028] - Tariq Shah; Muhammad Asad; Zeeshan Khan; Khadija Amjad; Abdulaziz Abdullah Alsahli; Roberto D'amato (Chemosphere, 2025)

Corrigendum to “Elucidating arsenic-induced stress responses in maize genotypes: Unravelling biochemical, physiological, and nutrient homeostasis for enhanced resilience” [Sci. Total Environ. 998 (2025) 180305] - Muhammad Ali Shah; Jiu Yang Mao; Rayyan Khan; Haseeb Ahmad; Shahid Ali; Kashif Khan; Muhammad Asad Naseer; Rida Rashid; Li Yang; Xun Bo Zhou (Science of The Total Environment, 2025)

Elucidating arsenic-induced stress responses in maize genotypes: Unravelling biochemical, physiological, and nutrient homeostasis for enhanced resilience - Muhammad Ali Shah; Jiu Yang Mao; Rayyan Khan; Haseeb Ahmad; Shahid Ali; Kashif Khan; Muhammad Asad Naseer; Rida Rashid; Li Yang; Xun Bo Zhou (Science of The Total Environment, 2025)

Offshore wind resource assessment and 7E analysis of offshore wind farms on the coastal belt of Pakistan - Talha Bin Nadeem; Asad A. Naqvi; Muhammad Saad; Kinza Malik; Ahsan Ahmed (Process Safety and Environmental Protection, 2025)

Depositional age and provenance of the Maziping Group, South China: Evidence from detrital zircon U–Pb dating and whole-rock geochemistry - Yasin Rahim; Huan Li; Thomas J. Algeo; Weidong Ren; Annan Guan; Mohammad Naseer; Zaheen Ullah; Asad Khan; Muhammad Yaseen; Mohamed Faisal (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Eco-friendly synthesis of N-doped carbon quantum dots from Bombax ceiba stem: A photophysical study with exploratory sensing of Fe3+/Cd2+ and dye degradation - Muhammad Arslan Akhtar; Jalwa Anum; Sameh S. Ahmed; Muhammad Ashfaq Ahmed; Asad Muhammad Khan; Christie M. Sayes; Abdur Rahim (Journal of Water Process Engineering, 2025)

Interaction of 4-nitrophenol with CTAB and CTAB/TX-100 mixed surfactant systems: A spectroscopic and thermodynamic study - Shanza Mujeeb; Asad Muhammad Khan (Journal of Environmental Chemical Engineering, 2025)

The challenges and progress of CAR-T cell therapy in the treatment of solid tumors - Kai Cui; Wanjun He; Na Huang; Songshan Zhu; Dan Jiang; Weiqiang Yang; Yiwei Zeng; Muhammad Asad Farooq; Guangxian Xu (Molecular and Cellular Biochemistry, 2025)

Evaluating the preclinical efficacy of naringenin in rheumatoid arthritis: a meta-analysis of in vivo studies - Muhammad Muzammil Nazir; Ayesha Batool; Muhammad Asad Sajid; Asma Ashraf (Inflammopharmacology, 2025)

Petrological and Re-Os isotopic constraints on the origin of chromitites and peridotites of the late cretaceous Waziristan ophiolite, western Pakistan: implications for subduction initiation - Zaheen Ullah; Asad Khan; Huan Li; Scott A. Whattam; Muhammad Tahir Shah; Liaqat Ali; Shah Faisal; Tehseen Zafar; Muhammad Farhan; Shuja Ullah; Syed Tanvir Shah; Zahid Hussain; et al. (International Geology Review, 2025)

Papaya leaf extract: A potential ally against dengue-induced thrombocytopenia in low-income countries- a mini review - Muhammad Noman Siddiqui; Ahmed Asad Raza; Aysha Asif; Abedin Samadi (Next Research, 2025)

Green-synthesized amino-rich carbon quantum dots: A dual-function platform for fluorescent detection of heavy metals and degradation of malachite green dye - Jalwa Anum; Muhammad Arslan Akhtar; Asad Muhammad Khan; Khalid Ahmed; Christie M. Sayes; Ali Madi Almajwal; Jibran Iqbal; Abdur Rahim (Journal of Water Process Engineering, 2025)

Roles of Fox gene in the development and reproduction of diamondback moth - Anam Noreen Abbas; Mubashir Tariq; Faisal Munir; Uroosa Zaheer; Ibrahim Adam; Muhammad Asad; Guang Yang (Journal of Insect Physiology, 2025)

A comprehensive review on the recovery of lithium from lithium-ion batteries and spodumene - Asad Ali; Sadia Afrin; Abdul Hannan Asif; Yasir Arafat; Muhammad Rizwan Azhar (Journal of Environmental Management, 2025)

Ultrahigh dielectric tunability at low voltage in PVDF nanocomposite driven by nonlinear ZnO-ferroelectric core-shell architecture for microwave device application - Arif Hussain; Suibin Luo; Can Zhao; Jie Liu; Asad Muhammad Khan; Shuhui Yu (Chemical Engineering Journal, 2025)

Evolving climatic patterns and drought risk in Pakistan’s agro-ecological zones - Raja Muhammad Usama; Sawaid Abbas; Mansour Almazroui; Muhammad Fahad Bilal; Asad Ali (Theoretical and Applied Climatology, 2025)

Correction: Interactive Effect of Genotype and Zinc Sulphate Improves Productivity and Grain Biofortification of Bread Wheat in Alkaline Soils - Sami Ul‑Allah; Farrukh Azeem; Ahad Madani; Ahmad Sher; Abdul Sattar; Muhammad Ijaz; Mojtaba Hassanzadehdelouei; Asad Azeem; Waqas Malik (Journal of Soil Science and Plant Nutrition, 2025)

Covalently grafting cationized sericin to silk fabric for achieving economical salt-free dyeing and antibacterial property and minimizing strength loss - Muhammad Asad Saleem; Zihao Jin; Mingbo Ma (Clean Technologies and Environmental Policy, 2025)

Effect of Different Levels of Copper Oxide (CuO) Nanoparticles and Biochar on Soil’s Microbial Activities and Maize (Zea Mays L.) Growth - Muhammad Abdullah Aziz; Sana Zahra; Bilal Adil; Amir Naserin; Muhammad Asad Hameed; Ijaz Ali; Temoor Ahmed; Ajaz Ahmad (Journal of Soil Science and Plant Nutrition, 2025)

Cyto-genotoxic assessment of bisphenol P through expression of DNA damage/repair genes in MDBK cell line - Muhammad Muddassir Ali; Samra Afzal; Maryam Javed; Imran Rashid; Furqan Awan; Asad Ullah; Tanveer Majeed; Hadeer Darwish; Ahmed Noureldeen; Jawaher Albaqami; Khalid Mehmood (In Vitro Cellular & Developmental Biology - Animal, 2025)

Utilizing genetic resources to develop yellow rust-resistant and high-yielding wheat genotypes across diverse environments - Hassan Mujtaba; Fahim Ullah Khan; Muhammad Sufyan; Israr Ud Din; Manzoor Ahmad; Asad Shah; Umair Bin Qasim (Genetic Resources and Crop Evolution, 2025)

Mechanisms of lime-induced N2O mitigation in acidic soils: A meta-analysis of microbial activity and substrate dynamics - Kiya Adare Tadesse; Tianfu Han; Zhe Shen; Nano Alemu Daba; Jiwen Li; Muhammad Numan Khan; Asad Shah; Huimin Zhang (Applied Soil Ecology, 2025)

Spatio-temporal assessment of heavy metal contamination in groundwater along Madhuana drain, Faisalabad: source apportionment and health risk analysis - Muhammad Hassan Bashir; Abubakar Asif; Hamaad Raza Ahmad; Asad Abbas; Muhammad Tahir Shehzad (Environmental Geochemistry and Health, 2025)

Effect of Graphene Nanosheets on the Histological Abnormalities in the Liver and Intestine of Cirrhinus mrigala Treated with Plant Extracts of Tamarix aphylla and Albizia lebbeck - Aisha Fatima; Muhammad Asad; Tehseen Fatima; Fan Renqing; Kinza Fatima; Liu Manhong (Bulletin of Environmental Contamination and Toxicology, 2025)

Quantum Chemical Insights into Metal-Ion Enhanced NLO Response of a Fluorescent Probe for Advanced Sensing Application - Asad Ullah; Muhammad Arif Ali; Sabir Ali Siddique; Muhammad Ibrahim; Hong Liang Xu; Abdul Rauf; Amal M. Al-Mohaimeed; Wedad A. Al-onazi; Muhammad Arshad (Journal of Fluorescence, 2025)

The biocontrol activity of both Bacillus thuringiensis and Beauveria bassiana against Spodoptera litura and their toxic effect on the insect metamorphosis - Muhammad Arshad; Asad Abdullah; Muhammad Irfan Ullah; Lamya Ahmed Alkeridis; Ohud Muslat Aharthy; Seham Sater Alhelaify; Nahdia Perveen; Malaika Shaheen; Asad Mehmood; Samy Sayed (International Journal of Tropical Insect Science, 2025)

Molecular modeling to design a multiepitope vaccine against emerging tick-borne Yezo virus and its validation through biophysics techniques - Hassan Ayaz; Muhammad Suleman; Asad Ali Shah; Syed Ainul Abideen; Faisal Ahmad; Muhammad Ali; Sajjad Ahmad; Asia Nawaz; Hanbal Ahmad khan; Inam Hussain; Muhammad Irfan; Yasir Waheed (In Silico Pharmacology, 2025)

Removal of nickel ions from industrial wastewater using tms-EDTA-functionalized Ti3C2Tx: Experimental and statistical physics modeling - Syed Asad Raza Kazmi; Syed Muhammad Husnain; Abdul Rehman Khan; Tariq M. Qureshi; Tarek Lemaoui; Inas M. AlNashef; Hassan A. Arafat; Faisal Shahzad (Journal of Hazardous Materials, 2025)

Green-engineered calcium-doped carbon nanospheres enhance salt tolerance and growth in maize by modulating gene expressions and antioxidant defense mechanisms - Muhammad Haseeb Javaid; Bahar Ali; Asifa Neelam; Syed Asad Hussain Bukhari; Raheel Munir; Zulqarnain Haider; Muhammad Rehman; Hafiza Arooj Razzaq; Abdul Majeed; Yinbo Gan (Journal of Environmental Chemical Engineering, 2025)

Unravelling the role of non-covalent interactions using imidazolium and amino acid based organic salts for efficient CO2 capture: experimental, DFT and COSMO-RS explorations - Hira Karim; Sabahat Sardar; Asad Mumtaz; Anila Tabassum; Muhammad Arfan; Azhar Mahmood; Jean-Marc Leveque; Cecilia Devi Wilfred; Syed Farooq Adil; Mohammad Rafe Hatshan; Mujeeb Khan (Journal of Environmental Chemical Engineering, 2025)

Interesterification of waste cooking oil via microwave irradiation for glycerol-free biodiesel production - Muhammad Umer Qadeer; Muhammad Ayoub; Muhammad Hamza Nazir; Muhammad Asad Javed; Zulqarnain; Imtisal Zahid; Mariam Ameen; Farooq Sher; Alhassan Ibrahim (Biomass and Bioenergy, 2025)

An automatic approach for the classification of lumpy skin disease in cattle - Fakhre Alam; Asad Ullah; Mohammed A. Rohaim; Muhammad Munir; Aftab Hussain (Tropical Animal Health and Production, 2025)

Interactive Effect of Genotype and Zinc Sulphate Improves Productivity and Grain Biofortification of Bread Wheat in Alkaline Soils - Sami Ul-Allah; Farrukh Azeem; Ahad Madani; Ahmad Sher; Abdul Sattar; Muhammad Ijaz; Mojtaba Hassanzadehdelouei; Asad Azeem; Waqas Malik (Journal of Soil Science and Plant Nutrition, 2025)

Assessing the Role of Biostimulants in Affecting the Production of Radish and Eggplant - Muhammad Amjad Bashir; Qurat-Ul-Ain Raza; Abdur Rehim; Hafiz Muhammad Ali Raza; Asad Ismail Noor; Mir Sujaul Islam; Faiz-Ul-Hassan; Muhammad Zafar-Ul-Hye; Yucong Geng (Journal of Soil Science and Plant Nutrition, 2025)

Root Diameter-Associated Exudates Drive the Changes in Rhizosphere Microbial communities - Huabo Du; Butian Wang; Muhammad Dawood; Peng Qu; Weifeng Li; Lingyan Zhang; Syed Asad Hussain Bukhari; Xuedong Shi; Meijun Qi; Shilang Dong; Yu Ge (Journal of Soil Science and Plant Nutrition, 2025)

Innovative drought monitoring: development and application of the multi-regional aggregated standardized drought index (MRASDI) - Asad Ellahi; Ibrahim A. Nafisah; Mohammed M. A. Almazah; Nafisa A. Abasheir; Ijaz Hussain; Muhammad Mubashar Dogar (Earth Science Informatics, 2025)

Assessment of Exploited Stock and Management Implications of Tiger Tooth Croaker (Otolithes ruber) in Coastal Waters of Makran, Pakistan - Samroz Majeed; S M Nurul Amin; Asad Ullah Ali Muhammad; Sudheer Ahmed (Fishes, 2025)
Pakistan’s marine fishing industry is crucial to the country’s economy, generating employment opportunities and foreign revenue. It produces 80% of the country’s total fish production. Otolithes ruber is a commercially important fish on the Makran coast of Pakistan, contributing significantly to the region’s croaker fisheries. This study is the first to apply three length-based approaches for assessing the stock status of O. ruber in the Makran coast: (1) TropFishR to estimate the mortality, growth parameters, and current exploitation status, reference points based on the yield per recruitment model, (2) the length-based Bayesian biomass method (LBB) to calculate stock biomass, and (3) the length-based spawning potential ratio (LBSPR) to estimate the spawning potential ratio. The length–weight relationship of Otolithes ruber was a positive allometric pattern (b = 3.28; R2 = 0.94). Growth parameters for Otolithes ruber were L∞ = 55.47 cm, K = 0.50 year−1. The calculated total mortality rate (Z), natural mortality (M), and fishing mortality (F) were 2.27 year−1, 0.67 year−1, and 1.6 year−1, respectively. The exploitation rate (E) was 0.70, indicating severe overexploitation. The current length at first capture (Lc50) = 27.37 cm was lower than that at first maturity (Lm50) = 30.75 cm, indicating growth overfishing. The current spawning potential ratio (8%) was lower than the optimal value (40%), indicating recruitment overfishing. The current biomass, concerning virgin biomass B/Bo, was also 8%, resulting in a 92% stock decline. We recommend reducing the exploitation pressure by limiting the commercial catch to an optimum length range of 34.5–42.2 cm and reducing fishing pressure by 40% to ensure sustainable fishery management.

A comprehensive review on the bioactivity and pharmacological attributes of Withania somnifera - Muhammad Usman Khalid; Muhammad Tauseef Sultan; Iqra Baig; Asad Abbas; Ahmad Mujtaba Noman; Abdellah Zinedine; Elena Bartkiene; João Miguel Rocha (Natural Product Research, 2025)

Identifying and prioritizing risks in urban rainwater harvesting projects: an ISM-MICMAC approach for sustainable water resources management - Ammara Ali; Sanna Ullah; Muhammad Asad Ali; Muhammad Umar Farooq; Wajih Ur Rehman; Mehdi Tlija (Stochastic Environmental Research and Risk Assessment, 2025)

Correction: Development of prediction models for strength properties of concrete using gene expression programming - Asad Ullah Khan; Muhammad Faisal Javed; Majid Khan (Innovative Infrastructure Solutions, 2025)

Heavy metal contamination in some commercial marine fishes of Pakistan - Sania Riaz; Muhammad Javed Khan; Iqra Rani; Asad Ali; Muhammad Asghar Qazi; Mehnoor Sameer; Khadija; Nimra Hussain; Shahid Sherzada (Food Additives & Contaminants Part B-Surveillance, 2025)

Shaping rhizocompartments and phyllosphere microbiomes and antibiotic resistance genes: The influence of different fertilizer regimes and biochar application - Kedi Li; Saeed ur Rahman; Asad Rehman; Haoxiang Li; Nan Hui; Muhammad Khalid (Journal of Hazardous Materials, 2025)

Accelerating crop improvement via integration of transcriptome-based network biology and genome editing - Izreen Izzati Razalli; Muhammad-Redha Abdullah-Zawawi; Amin-Asyraf Tamizi; Sarahani Harun; Rabiatul-Adawiah Zainal-Abidin; Muhammad Irfan Abdul Jalal; Mohammad Asad Ullah; Zamri Zainal (Planta, 2025)

Immunological assessment of NSFu1: A novel fusion molecule constructed from structural proteins of SARS-CoV-2 for improving COVID-19 antibody detection - Shaista Arif; Mohsina Akhter; Aqsa Anwar; Sania Javaid; Zara Ashi; Mohsin Shad; Asad Rahman; Huda Abbas; Fouzia Ashraf; M. Waheed Akhtar; Muhammad Sajjad (Archives of Microbiology, 2025)

Melatonin mitigates nickel oxide nanoparticles induced phytotoxicity in soybean by reducing metal accumulation, enhancing antioxidant defense and promoting nitrogen assimilation - Kashif Khan; Rayyan Khan; Zhuo Liu; Shahid Ali; Muhammad Asad Naseer; Muhammad Ali Shah; Haseeb Ahmad; Xun Bo Zhou (Journal of Hazardous Materials, 2025)

Retraction notice to “Alleviation of microplastic toxicity in soybean by arbuscular mycorrhizal fungi: Regulating glyoxalase system and root nodule organic acid” [J. Environ. Manag. 349 (2024) 119377] - Zeeshan Khan; Tariq Shah; Muhammad Asad; Khadija Amjad; Abdulaziz Abdullah Alsahli; Parvaiz Ahmad (Journal of Environmental Management, 2025)

Retraction notice to “Straw incorporation into microplastic-contaminated soil can reduce greenhouse gas emissions by enhancing soil enzyme activities and microbial community structure” [J. Environ. Manag. 351 (2024) 119616] - Tariq Shah; Zeeshan Khan; Muhammad Asad; Ayesha Imran; Muhammad Bilal Khan Niazi; Raf Dewil; Ajaz Ahmad; Parvaiz Ahmad (Journal of Environmental Management, 2025)

Designing of efficient CoLa2O4/V-Ag-MOF hybrid electrode for energy storage, hydrogen evolution reaction, and chemical sensors - Asad Ur Rehman; Nimra Muzaffar; Imad Barsoum; Amir Muhammad Afzal; Muhammad Ali; Muhammad Waqas Iqbal; Zubair Ahmad; Sohail Mumtaz; Aboud Ahmed Awadh Bahajjaj; Shaik Abdul Munnaf (Fuel, 2025)

Role of artificial intelligence in halal authentication and traceability: A concurrent review - Asad Nawaz; Atka Afzal; Ali Khatibi; Amar Shankar; Heena Madan; Hafiza Sana Faisal; Amna Shahbaz; Ifrah Usman; Nimra Zulfiqar; Farhan Saeed; Aftab Ahmed; Ali Imran; et al. (Food Control, 2025)

Development of prediction models for strength properties of concrete using gene expression programming - Asad Ullah Khan; Muhammad Faisal Javed; Majid Khan (Innovative Infrastructure Solutions, 2025)

RETRACTED ARTICLE: Optimizing callogenesis in five potential medicinal herbs for the bioactive constituents: a sustainable approach to pharmaceutical production - Muhammad Wasim Haider; Muhammad Nafees; Maryyam Bint-e-Tariq; Umar Farooq; Tanveer Hussain; Taki Demir; Asad Masood; Muhammad Samsam Raza; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Ozhan Simsek; Temoor Ahmed; et al. (Genetic Resources and Crop Evolution, 2025)

Material selection in the construction industry: a systematic literature review on multi-criteria decision making - Asad Ur Rehman Bajwa; Chandana Siriwardana; Wajiha Shahzad; Muhammad Ahmad Naeem (Environment Systems and Decisions, 2025)
Material choice is critical for ensuring sustainability in the construction industry. Higher carbon embodiment materials contribute towards greenhouse gas emissions and global warming. Decisions on sustainable material selection depend on multiple criteria and variables, thus creating a difficulty to determine the best choice. Multi-Criteria Decision Making (MCDM) techniques have the potential to address this challenge. However, there is limited data that reviews MCDM in choosing building and construction materials. This study aims to review the MCDM methods employed in the sustainable selection of building materials within the construction industry. This systematic literature review (SLR) incorporates meta-analysis and thematic mapping through applying “PRISMA framework” and “ Bibliometrix ”, respectively. This study explored and analysed the records published from 2010 to 2023. This work identified the critical steps for addressing decision problems in building material selection: Establishing criteria, ranking the hierarchy, comparing the selection criteria, and enabling consistency indices. Moreover, one of the most used MCDM methods, i.e. Analytical Hierarchy Process (AHP) was particularly found particularly useful for the selection criteria and weight assignment of variables regarding the waste, recycled, and composite materials. The involvement of several criteria and alternatives raised the complexity of decision problems, leading to the use of Hybrid MCDM. Hybrid MCDM techniques possess the capacity guide informed decisions for the sustainable material selection in the construction industry.

Mycorrhizopshere bacteria alleviated arsenic toxicity by regulating organic acids, glyoxalase defense system, and metal transporters in soybean plants - Zeeshan Khan; Shahrukh Khan; Mansour I. Almansour; Muhammad Asad; Mohammad Javed Ansari; Hamad Khan; Ijaz Ahmad (South African Journal of Botany, 2025)

Corrigendum to ‘The protective roles of Oryza glumaepatula and phytohormone in enhancing rice tolerance to cadmium stress by regulating gene expression, morphological, physiological, and antioxidant defense system’ [Environ. Pollut. 364P1 (2024) 125311] - Humera Ashraf; Fozia Ghouri; Shafaqat Ali; Syed Asad Hussain Bukhari; Fasih Ullah Haider; Minghui Zhong; Weiwei Xia; Xuelin Fu; Muhammad Qasim Shahid (Environmental Pollution, 2025)

Green synthesized silicon dioxide nanoparticles (SiO2NPs) ameliorated the cadmium toxicity in melon by regulating antioxidant enzymes activity and stress-related genes expression - Muhammad Sanaullah Malik; Asad Rehman; Iftikhar Hussain Shah; Samiah Arif; Kai Nan; Yumeng Yan; Shiren Song; Muhammad Khalid Hameed; Muhammad Azam; Yidong Zhang (Environmental Pollution, 2025)

Exploring hotspots of traffic accidents in Chiniot-Sargodha Road, Punjab, Pakistan - Taimoor Ashraf; Muhammad Irfan Ahamad; Shakeel Mahmood; Jiangtao Fu; Muhammad Sajid Mehmood; Adnanul Rehman; Sohail Abbas; Syed Ali Asad Naqvi; Rana Muhammad Zulqarnain (Environment, Development and Sustainability, 2025)

Band Gap Tuning in Mercaptoacetic Acid Capped Mixed Halides Perovskites and Effect of Solvents on Their Fluorescence Dynamics: A Potential Sensor for Polarity - Muhammad Asad Riaz; Usman Zahid; Maria Mukhtar; Muhammad Adnan Khalid; Muhammad Mubeen; Azhar Iqbal (Journal of Fluorescence, 2025)

Cross-climatic comparison of microbial stress-responsive genes in urban parks: A comparative analysis - Saeed ur Rahman; Xinxin Liu; Muhammad Khalid; Asad Rehman; Junfeng Cao; Chang Zhao; Haoxin Tan; Samiah Arif; Bangxiao Zheng; Yucheng Bian; Ari Jumpponen; D. Johan Kotze; et al. (Urban Forestry & Urban Greening, 2025)

Residual effects of biochar and nano-modified biochar on growth and physiology under saline environment in two different genotype of Oryza sativa L. - Haider Sultan; Hafiz Muhammad Mazhar Abbas; Mohammad Faizan; Abolghassem Emamverdian; Asad Shah; Saraj Bahadur; Yusheng Li; Mohammad Nauman Khan; Lixiao Nie (Journal of Environmental Management, 2025)

The protective roles of Oryza glumaepatula and phytohormone in enhancing rice tolerance to cadmium stress by regulating gene expression, morphological, physiological, and antioxidant defense system - Humera Ashraf; Fozia Ghouri; Shafaqat Ali; Syed Asad Hussain Bukhari; Fasih Ullah Haider; Minghui Zhong; Weiwei Xia; Xuelin Fu; Muhammad Qasim Shahid (Environmental Pollution, 2025)

Combating Lead (Pb) Contamination: Integrating Biomonitoring, Advanced Detection, and Remediation for Environmental and Public Health - Saima Zafar; Sehrish Fatima; Farkhanda Asad; Muhammad Muzammil Nazir; Sania Batool; Asma Ashraf (Water, Air, & Soil Pollution, 2025)

Optimizing support vector machines for enhanced permeability prediction in sandstone reservoirs using systematic and heuristic hyperparameter tuning - Jar Ullah; Huan Li; Rifaat M. Abdalla; Muhammad Asad; Amos P. K. Tai; Asim Falaknaz (Earth Science Informatics, 2025)

Optimization of hydrogen production using a coculture of Chlamydomonas reinhardtii and activated sludge bacteria - Abdelsalam Zidan; Muhammad Asad Javed; Ashraf Aly Hassan (Chemosphere, 2024)

Effect of differential exposure of UV-C and melatonin stress on the therapeutic potential of bioactive compounds in Moringa oleifera - Muhammad Naeem Bajwa; Gouhar Zaman; Muhammad Asad Ullah; Muhammad Uzair Javed; Anisa Andleeb; Christophe Hano; Bilal Haider Abbasi (South African Journal of Botany, 2024)

Rice and heavy metals: A review of cadmium impact and potential remediation techniques - Weiwei Xia; Fozia Ghouri; Minghui Zhong; Syed Asad Hussain Bukhari; Shafaqat Ali; Muhammad Qasim Shahid (Science of The Total Environment, 2024)

Microbial-inoculated biochar for remediation of salt and heavy metal contaminated soils - Hafiz Muhammad Mazhar Abbas; Ummah Rais; Muhammad Mohsin Altaf; Fahd Rasul; Asad Shah; Ashar Tahir; Muhammad Nafees-Ur-Rehman; Muhammad Shaukat; Haider Sultan; Ruilong Zou; Mohammad Nauman Khan; Lixiao Nie (Science of The Total Environment, 2024)

Development of growth curve and estimation of genetic parameters of Nili-Ravi buffalo calves from birth to one year of age through non-linear models - Asad Abbas; Atia Basheer; Moinina Nelphson Kallon; Numan Sharif; Heydar Ghiasi; Tariq Mehmood; Burhane Azam; Anjum Khalique; Muhammad Dawood; Imran Zahoor (Tropical Animal Health and Production, 2024)

The association of ABCB1 gene polymorphism with clinical response to carbamazepine monotherapy in patients with epilepsy - Haroon Ur Rashid; Shakir Ullah; Daniel F. Carr; Muhammad Ijaz Khan Khattak; Muhammad Imran Asad; Mujeeb Ur Rehman; Muhammad Khalid Tipu (Molecular Biology Reports, 2024)

Bridging drug discovery through hierarchical subtractive genomics against asd, trpG, and secY of pneumonia causing MDR Staphylococcus aureus - Ayesha Wisal; Nida Saeed; Muhammad Aurongzeb; Muhammad Shafique; Saman Sohail; Waheed Anwar; Zarrin Basharat; Muhammad Irfan; Asad Ullah; Syed S. Hassan (Molecular Genetics and Genomics, 2024)

Global microplastics pollution: a bibliometric analysis and review on research trends and hotspots in agroecosystems - Asad Jamil; Ambreen Ahmad; Muhammad Irfan; Xin Hou; Yi Wang; Ziwei Chen; Xianhua Liu (Environmental Geochemistry and Health, 2024)

Comparative analysis of mechanical characteristics in masonry walls: impact of aspect ratios and opening percentages - Ubaid Ahmad Mughal; Asad Ullah Qazi; Ali Ahmed; Umbreen Us Sahar; Muhammad Mubashir Ajmal (European Journal of Environmental and Civil Engineering, 2024)

Nutritional composition assessment and antimicrobial activity of Catostylus perezi , jellyfish blooms along the coast of Pakistan: an awareness to avoid food neophobia in Pakistan - Muhammad Naveed; Malik Wajid Hussain Chan; Sadar Aslam; Fenghuan Wang; Anas Sajjad; Asad Ullah; Nida Saleem; Muhammad Samee Haider; Victoria Arija (Natural Product Research, 2024)

Microscale urban heat variability and time-location patterns: Elevated exposure for bikers and rickshaw drivers beyond average city temperatures in megacity - Bilal Ahmed Usmani; Muhammad Ahmed; Tahani Waqar; Asad Allana; Zafar Ahmed; Zafar Fatmi (Urban Climate, 2024)

Enhancing degradation of PLA-made rigid biodegradable plastics with non-thermal plasma treatment - Muhammad Ajmal; Muhammad Asad; Weizhong Huo; Yuchao Shao; Wenjing Lu (Journal of Cleaner Production, 2024)

Spatio-temporal analysis of hydrometeorological variables for terrestrial and groundwater storage assessment - Muhammad Shareef Shazil; Sheharyar Ahmad; Syed Amer Mahmood; Syed Ali Asad Naqvi; Sanju Purohit; Aqil Tariq (Groundwater for Sustainable Development, 2024)

Extraction of bioactive components from date palm waste, various extraction processes and their applications: A review - Imtisal Zahid; Muhammad Hamza Nazir; Muhammad Asad Javed (Biomass and Bioenergy, 2024)

Comprehensive insights on treatment modalities with conventional and herbal drugs for the treatment of duodenal ulcers - Huma Hameed; Jahangir Hussain; Ana Cláudia Paiva-Santos; Muhammad Zaman; Ali Hamza; Irsa Sajjad; Faria Asad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Co-production and enhancement of biogas and biohydrogen by optimizing NaOH-urera pretreatment conditions for kitchen waste - Asad A. Zaidi; Sohaib Z. Khan; Hamad Almohamadi; Mohammad Rehan; Muhammad Abdul Qyyum (Process Safety and Environmental Protection, 2024)

Nutritional benefits of bioactive compounds from watermelon: A comprehensive review - Parkash Meghwar; Syed Muhammad Ghufran Saeed; Asad Ullah; Emmanuel Nikolakakis; Eirini Panagopoulou; Alexandros Tsoupras; Slim Smaoui; Amin Mousavi Khaneghah (Food Bioscience, 2024)

Nanoparticle-mediated modulation of plant performance and microbiome dynamics: Insights into interplay mechanisms - Kedi Li; Haoxiang Li; Saeed ur Rahman; Asad Rehman; Muhammad Khalid (Biocatalysis and Agricultural Biotechnology, 2024)

An integrated land change modeler and distributed hydrological model approach for quantifying future urban runoff dynamics - Asad Hussain Muhammad; Waseem Muhammad; Ajmal Muhammad; Atiq Ur Rehman Tariq Muhammad; Jiaqing Xiao; Tao Yang; Pengfei Shi (Science China Earth Sciences, 2024)

Neoproterozoic granitoids of northwest Vietnam and their tectonic implications - Ngo Xuan Dac; Asad Khan; Zaheen Ullah; Trinh Hai Son; Li Xiao Chun; Khuong The Hung; Guanzhong Shi; Duan Zhuang; Muhammad Farhan (International Geology Review, 2024)

Soil organic carbon regulation by pH in acidic red soil subjected to long-term liming and straw incorporation - Zhe Shen; Tianfu Han; Jing Huang; Jiwen Li; Nano Alemu Daba; Ntagisanimana Gilbert; Muhammad Numan Khan; Asad Shah; Huimin Zhang (Journal of Environmental Management, 2024)

From port to planet: Assessing NO2 pollution and climate change effects with Sentinel-5p satellite imagery in maritime zones - Mohd Azhafiz Abdullah; L.F. Chuah; Samsuri Bin Abdullah; Awais Bokhari; Asad Syed; Abdallah M. Elgorban; Muhammad Saeed Akhtar; Hind A. AL-Shwaiman; Saira Asif (Environmental Research, 2024)

Tailoring structural and optical properties of Cu(II)-induced MgAl2O4 nanoparticles and their response to toxic dyes under solar illumination - Muhammad Javed; Naeem Akbar; Ayaz Arif Khan; Asad Masood; Naeem Ahmed; Muhammad Junaid Khan; Nisar Ahmed; Said Nasir Khisro; Muhammed Ali Shaikh Abdul Hameed (Environmental Science and Pollution Research, 2024)

Tree-ring based summer temperature variability since 1790 CE in the Hindu Kush region of northern Pakistan - Fayaz Asad; Muhammad Adil; Sabrina Shahid; Nasrullah Khan; Ru Huang; Haifeng Zhu (International Journal of Biometeorology, 2024)

Investigation of torsion in confined masonry structures originating due to unsymmetric openings - Ubaid Ahmad Mughal; Asad Ullah Qazi; Ali Ahmed; Muhammad Mubashir Ajmal; Muhammad Danish (European Journal of Environmental and Civil Engineering, 2024)

Green-synthesized lignin nanoparticles enhance Zea mays resilience to salt stress by improving antioxidant metabolism and mitigating ultrastructural damage - Muhammad Haseeb Javaid; Nana Chen; Muhammad Umair Yasin; Xingming Fan; Asifa Neelam; Muhammad Rehman; Zulqarnain Haider; Syed Asad Hussain Bukhari; Raheel Munir; Irshan Ahmad; Yinbo Gan (Chemosphere, 2024)

Evaluating climate change impacts on reef environments via multibeam echosounder and Acoustic Doppler Current profiler technology - Mohd Azhafiz Abdullah; L.F. Chuah; Razak Zakariya; Asad Syed; Rozaimi Che Hasan; Shahrul Miza Mahmud; Abdallah M. Elgorban; A. Bokhari; Muhammad Saeed Akhtar; Hind A. AL-Shwaiman (Environmental Research, 2024)

Characteristics and health implications of fine particulate matter near urban road site in Islamabad, Pakistan - Sabir Hussain; Azhar Siddique; Mujtaba Hassan; Kashif Rasool; Asif Shahzad; Syed Ali Asad Naqvi; Muhammad Raza Ul Mustafa (Environmental Research, 2024)

Design and optimization of off-grid solar PV and biomass-based hybrid renewable energy system (HRES) for electrification of a rural community in Tharparkar, Pakistan - Talha Bin Nadeem; Ahsan Ahmed; Muhammad Saad; Asad A. Naqvi (Environment, Development and Sustainability, 2024)

Towards artificial intelligence empowered performance enhancement of EDM process using nano-graphene mixed bio-dielectric supporting the carbon neutrality and sustainable development - Kashif Ishfaq; Muhammad Asad; Waqar Muhammad Ashraf; Muhammad Sana; Saqib Anwar; Wei Zhang; Vivek Dua (Journal of Cleaner Production, 2024)

Green synthesis of silver nanoparticles for their antifungal activity against anthracnose disease causing Colletotrichum capsici - Anum Haq Nawaz; Ansar Mehmood; Abd ur Rehman Khalid; Muhammad Abdul Rauf Khan; Gul-e-lala; Khawaja Shafique Ahmad; Asad Ghulam Nabi (Biocatalysis and Agricultural Biotechnology, 2024)

Potential use of maize–peanut intercropping to adapt to drought and nitrogen–shortage impacts - Fei Han; Shuqing Guo; Muhammad Asad Naseer; Ru Guo; Tie Cai; Peng Zhang; Zhikuan Jia; Dong Yang; XiaoLi Chen; Xiaolong Ren (Plant and Soil, 2024)

Zinc oxide application alleviates arsenic-mediated oxidative stress via physio-biochemical mechanism in rice - Sanaullah Jalil; Muhammad Mudassir Nazir; Mohamed A. Eweda; Faisal Zulfiqar; Temoor Ahmed; Muhammad Noman; Muhammad A. U. Asad; Kadambot H. M. Siddique; Xiaoli Jin (Environmental Science and Pollution Research, 2024)

Exposure to zinc oxide nanoparticles induced reproductive toxicities in male Sprague Dawley rats - Nagina Rehman; Farhat Jabeen; Muhammad Asad; Aneela Nijabat; Amir Ali; Safir Ullah Khan; Juan Pedro Luna-Arias; Zia-ur-Rehman Mashwani; Ayesha Siddiqa; Adhimoolam Karthikeyan; Ajaz Ahmad (Journal of Trace Elements in Medicine and Biology, 2024)

Modulating plant-soil microcosm with green synthesized ZnONPs in arsenic contaminated soil - Asad Rehman; Saeed ur Rahman; Pengli Li; Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Muhammad Azam; Junfeng Cao; Muhammad Sanaullah Malik; Mouna Jeridi; Naveed Ahmad; Khulood Fahad Alabbosh; Qunlu Liu; et al. (Journal of Hazardous Materials, 2024)

Clubroot (Plasmodiophora brassicae) Suppression Under Biocontrol Agents in Pak choi with Variations in Physiological, Biochemical, and Bacterial Diversity - Shazma Gulzar; Fiza Liaquat; Muhammad Khalid Hameed; Asad Rehman; Muhammad Salman Zahid; Muhammad Aamir Manzoor; Iftikhar Hussain Shah; Yidong Zhang (Journal of Plant Growth Regulation, 2024)

Identification of synthetic wheat lines with broadly effective stripe rust resistance - Karanjeet S. Sandhu; Davinder Singh; Fikrte Y. Belayineh; Tamrat Negash; Hanif Khan; Subhash C. Bhardwaj; Suraj Baidya; Dhruba B. Thapa; Muhammad Fayyaz; Shahzad Asad; Mandeep S. Randhawa; Robert F. Park (Australasian Plant Pathology, 2024)
Wheat stripe/yellow rust (WYR), caused by Puccinia striiformis f. sp. tritici ( Pst ), is a major constraint in global wheat production. A set of 766 hexaploid synthetic wheat lines, including primary crosses of Triticum turgidum x Aegilops tauschii and their derivatives, were screened in artificially rust inoculated field nurseries for three seasons. From this set, a core set of 94 non-lodging lines with unique pedigrees and resistance to Pst that was consistent across years was established. The core set was tested for adult plant field response under field conditions for three seasons in Australia and at least one crop season in Ethiopia, India, Kenya, Nepal and Pakistan. It was also challenged with an array of well-defined Pst pathotypes at seedling growth stages in the greenhouse, and genotyped with molecular markers linked to the adult plant resistance (APR) genes Yr18 , Yr36 and Yr46 . Combined analysis of field rust responses, multi-pathotype seedling phenotyping and marker genotyping resolved seven classes of Pst resistance: uncatalogued (new) APR (UAPR, 11%), uncatalogued seedling resistance (USR, 46%), known seedling resistance (KSR, 5%), KSR + USR (2%), Yr18 + UAPR (4%), Yr18 + USR (29%) and Yr18 + KSR (3%). A majority of the lines carrying UAPR and USR either singly or in combination showed high levels of field resistance across all field sites and years of testing, demonstrating that these lines represent a valuable resource for breeding wheat for resistance to Pst .

From field to table: Ensuring food safety by reducing pesticide residues in food - Salman Munir; Asad Azeem; Muhammad Sikandar Zaman; Muhammad Zia Ul Haq (Science of The Total Environment, 2024)

Potential of Capparis decidua plant and eggshell composite adsorbent for effective removal of anionic dyes from aqueous medium - Ghulam Mujtaba; Abdul Hai; Mansoor Ul Hassan Shah; Asad Ullah; Yasir Anwar; Furqan Shah; Muhammad Daud; Afzal Hussain; Faheem Ahmed; Fawzi Banat (Environmental Research, 2024)

Differential capacity of phragmites ecotypes in remediation of inorganic contaminants in coastal ecosystems: Implications for climate change - Noreen Akhter; Muhammad Aqeel; Shazia; Muhammad Kashif Irshad; Muhammad Muslim Shehnaz; Sang Soo Lee; Ali Noman; Asad Syed; A. Bokhari; Ali H. Bahkali; Ling Shing Wong (Environmental Research, 2024)

Structural and thermal investigation of lignocellulosic biomass conversion for enhancing sustainable imperative in progressive organic refinery paradigm for waste-to-energy applications - Tayyab Qureshi; Muhammad Farooq; Shahid Imran; Muhammad Adeel Munir; Muhammad Asad Javed; Ihsanullah Sohoo; Muhammad Sultan; Ateekh Ur Rehman; Muhammad Farhan; Muhammad Asim; John M. Andresen (Environmental Research, 2024)

Exploring the impact of urbanization and vegetation type on fungal communities: Insights into divergent, mycorrhizal, and saprophytic associations driven by climate patterns - Muhammad Khalid; Saeed ur Rahman; Xinxin Liu; Asad Rehman; Ari Jumpponen; D. Johan Kotze; Heikki Setälä; Nan Hui (CATENA, 2024)

Correction to: Mycorrhizosphere bacteria inhibit chromium uptake and phytotoxicity by regulating proline metabolism, antioxidant defense system, and aquaporin gene expression in tomato - Tariq Shah; Zeeshan Khan; Tahani Awad Alahmadi; Ayesha Imran; Muhammad Asad; Shah Rukh Khan; Mohammad Javed Ansari (Environmental Science and Pollution Research, 2024)

Mycorrhizosphere bacteria inhibit chromium uptake and phytotoxicity by regulating proline metabolism, antioxidant defense system, and aquaporin gene expression in tomato - Tariq Shah; Zeeshan Khan; Tahani Awad Alahmadi; Ayesha Imran; Muhammad Asad; Shah Rukh Khan; Mohammad Javed Ansari (Environmental Science and Pollution Research, 2024)

Optimizing potassium and nitrogen fertilizer strategies to mitigate greenhouse gas emissions in global agroecosystems - Jiwen Li; Tianfu Han; Kailou Liu; Zhe Shen; Nano Alemu Daba; Kiya Adare Tadesse; Muhammad Numan Khan; Asad Shah; Zhufeng Wang; Huimin Zhang (Science of The Total Environment, 2024)

Concentration and distribution patterns of rare earth elements (REEs) in stream sediments of Pakistan - Zhihua Wang; Jun Hong; Xin Lin; Huishan Zhang; Yasir Shaheen Khalil; Naghma Haider; Mehboob Ur Rashid; Muhammad Jawad Zeb; Asad Ali Narejo (Journal of Geochemical Exploration, 2024)

Biochar and nano biochar: Enhancing salt resilience in plants and soil while mitigating greenhouse gas emissions: A comprehensive review - Haider Sultan; Yusheng Li; Waqas Ahmed; Mu yixue; Asad Shah; Mohammad Faizan; Aqeel Ahmad; Hafiz Muhammad Mazhar Abbas; Lixiao Nie; Mohammad Nauman Khan (Journal of Environmental Management, 2024)

Integrated straw-derived biochar utilization to increase net ecosystem carbon budget and economic benefit and reduce the environmental footprint - Ru Guo; Rui Qian; Muhammad Asad Naseer; Fei Han; Peng Zhang; Zhikuan Jia; Xiaoli Chen; Xiaolong Ren (Field Crops Research, 2024)

Expression of BSN314 lysozyme genes in Escherichia coli BL21: a study to demonstrate microbicidal and disintegarting potential of the cloned lysozyme - Muhammad Naveed; Sai Wen; Malik Wajid Hussain Chan; Fenghuan Wang; Sadar Aslam; Xian Yin; Baocai Xu; Asad Ullah (Brazilian Journal of Microbiology, 2024)

Molecular characterization of genes involved in tolerance of cadmium in Triticum aestivum (L.) under Cd stress - Asima Rasheed; Arwa Abdulkreem AL-Huqail; Baber Ali; Suliman Mohammed Suliman Alghanem; Asad Ali Shah; Farrukh Azeem; Muhammad Rizwan; Rahmah N. Al-Qthanin; Fathia A. Soudy (Journal of Hazardous Materials, 2024)

Sustainable electric discharge machining using alumina-mixed deionized water as dielectric: Process modelling by artificial neural networks underpinning net-zero from industry - Muhammad Sana; Muhammad Asad; Muhammad Umar Farooq; Saqib Anwar; Muhammad Talha (Journal of Cleaner Production, 2024)

Can straw recycling achieve sustainable agriculture at the smallholder level? A case in a semi-arid region - Rui Qian; Ru Guo; Qingxuan Yang; Muhammad Asad Naseer; Baoping Sun; Longlong Wang; Jian Zhang; Xiaolong Ren; Xiaoli Chen; Zhikuan Jia (Journal of Cleaner Production, 2024)

Comprehensive review: Effects of climate change and greenhouse gases emission relevance to environmental stress on horticultural crops and management - Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Wu Jinhui; Xuyang Li; Muhammad Khalid Hameed; Asad Rehaman; Pengli Li; Yidong Zhang; Qingliang Niu; Liying Chang (Journal of Environmental Management, 2024)

RETRACTED: Straw incorporation into microplastic-contaminated soil can reduce greenhouse gas emissions by enhancing soil enzyme activities and microbial community structure - Tariq Shah; Zeeshan Khan; Muhammad Asad; Ayesha Imran; Muhammad Bilal Khan Niazi; Raf Dewil; Ajaz Ahmad; Parvaiz Ahmad (Journal of Environmental Management, 2024)

Synthetic bacterial community derived from Astragalus mongholicus and plant-plant interactions inhibit cadmium uptake by modulating gene expression, antioxidant system and carbohydrate metabolism under cadmium contaminated soil - Tariq Shah; Zeeshan Khan; Muhammad Asad; Roberto D’amato; Abdulaziz Abdullah Alsahli; Parvaiz Ahmad (Journal of Environmental Chemical Engineering, 2024)

Enhancement in the production of phenolic compounds from Fagonia indica callus cultures via Fusarium oxysporum triggered elicitation - Taimoor Khan; Muhammad Uzair Javed; Tehreem Mahmood; Bushra Khan; Tariq Khan; Muhammad Asad Ullah; Razia Khurshid; Gouhar Zaman; Christophe Hano; Nathalie Giglioli-Guivarc’h; Bilal Haider Abbasi (In Vitro Cellular & Developmental Biology - Plant, 2024)

Characteristics of unconfined masonry walls under in-plane static and reverse-cyclic loading: a comparative numerical study - Muhammad Asad Naseer; Asad Ullah Qazi; Ubaid Ahmad Mughal; Muhammad Mubashir Ajmal; Ali Ahmed (European Journal of Environmental and Civil Engineering, 2024)

RETRACTED: Synergistic effect of silicon and arbuscular mycorrhizal fungi reduces cadmium accumulation by regulating hormonal transduction and lignin accumulation in maize - Shah Rukh Khan; Zubair Ahmad; Zeeshan Khan; Umair Khan; Muhammad Asad; Tariq Shah (Chemosphere, 2024)

Beyond contamination: Enhancing plant tolerance to arsenic through phytobial remediation - Saeed ur Rahman; Xinxin Liu; Muhammad Khalid; Asad Rehman; Junfeng Cao; Sadaf-Ilyas Kayani; Muhammad Naeem; Naveed Ahmad; Abid Ali Khan; Muhammad Aamir Manzoor; Chang Zhao; Haoxin Tan; et al. (South African Journal of Botany, 2024)

Effects of seasonal temperature regimes: Does Cyprinus carpio act as a health hazard during the construction of Suki Kinari hydropower project on Kunhar River in Pakistan? - Shan-e-hyder Soomro; Xiaotao Shi; Jiali Guo; Shaista Jalbani; Muhammad Asad; Muhammad Imran Anwar; Caihong Hu; Senfan Ke; Yanqin Bai; Yuanyang Wang (Science of The Total Environment, 2024)

A comprehensive evaluation of sustainable mineral resources governance in Pakistan: An analysis of challenges and reforms - Naqib Ullah Khan; Peng Zhongyi; Asad Ullah; Muhammad Mumtaz (Resources Policy, 2024)

Biosynthesized zinc oxide nanoparticles modulate the phytoremediation potential of Pennisetum giganteum and its rhizocompartments associated microbial community structure - Haoxiang Li; Asad Rehman; Saeed ur Rahman; Kedi Li; Tianrui Yang; Percy Akuetteh; Muhammad Khalid (Journal of Cleaner Production, 2024)

RETRACTED: Alleviation of microplastic toxicity in soybean by arbuscular mycorrhizal fungi: Regulating glyoxalase system and root nodule organic acid - Zeeshan Khan; Tariq Shah; Muhammad Asad; Khadija Amjad; Abdulaziz Abdullah Alsahli; Parvaiz Ahmad (Journal of Environmental Management, 2024)

Effect of multiwalled carbon nanotubes on compressive behavior of concrete at elevated temperature for mass concreting - Kashan Nisar; Muhammad Shahid Siddique; Muhammad Rizwan; Syed Hassan Farooq; Muhammad Usman; Asad Hanif (European Journal of Environmental and Civil Engineering, 2023)

RETRACTED: Responses of microbial communities in rhizocompartments of king grass to phytoremediation of cadmium-contaminated soil - Muhammad Khalid; Xinxin Liu; Saeed ur Rahman; Asad Rehman; Chang Zhao; Xiaoxiao Li; Bian Yucheng; Nan Hui (Science of The Total Environment, 2023)

Feeding ethogram of Antilochus coquebertii F. preying on Dysdercus koenigii - Adeel Mukhtar; Muhammad Usama Altaf; Muhammad Ikhlaq; Waqar Jaleel; Syed Muhammad Zaka; Asad Ali; Zahid Hanif (Journal of Asia-Pacific Entomology, 2023)

Recent advances in microalgae, insects, and cultured meat as sustainable alternative protein sources - Nayab Fatima; Mohammad Naushad Emambux; Amin N. Olaimat; Alexandros Ch Stratakos; Asad Nawaz; Agung Wahyono; Khalid Gul; Jiyong Park; Hafiz Muhammad Shahbaz (Food and Humanity, 2023)

Subtractive sequence analysis aided druggable targets mining in Burkholderia cepacia complex and finding inhibitors through bioinformatics approach - Syed Shah Hassan; Rida Shams; Ihosvany Camps; Zarrin Basharat; Saman Sohail; Yasmin Khan; Asad Ullah; Muhammad Irfan; Javed Ali; Muhammad Bilal; Carlos M. Morel (Molecular Diversity, 2023)

Influence of Nitrogen Application on Soil Chemical Properties, Nutrient Acquisition, and Enzymatic Activities in Rainfed Wheat/Maize Strip Intercropping - Sadam Hussain; Muhammad Asad Naseer; Fei Han; Ru Guo; Muhammad Saqib; Muhammad Farooq; Xiaoli Chen; Xiaolong Ren (Journal of Soil Science and Plant Nutrition, 2023)

Comparison of As removal efficiency and health risks from aqueous solution using as-synthesized Fe0 and Cu0: modelling, kinetics and reusability - Behzad Murtaza; Asad Ali; Muhammad Imran; Abdullah A. Al-Kahtani; Zeid A. ALOthman; Natasha Natasha; Muhammad Shahid; Noor S. Shah; Muhammad Asif Naeem; Sajjad Ahmad; Ghulam Murtaza (Environmental Geochemistry and Health, 2023)

Differential Response of Two Contrasting Melon (Cucumis melo L.) Genotypes to Drought Stress - Asad Rehman; Jinyang Weng; Pengli Li; Jing Yu; Saeed ur Rahman; Muhammad Khalid; Iftikhar Hussain Shah; Shazma Gulzar; Liying Chang; Qingliang Niu (Journal of Plant Biology, 2023)

Silicon inhibits cadmium uptake by regulating the genes associated with the lignin biosynthetic pathway and plant hormone signal transduction in maize plants - Tariq Shah; Zeeshan Khan; Shah Rukh Khan; Ayesha Imran; Muhammad Asad; Ajaz Ahmad; Parvaiz Ahmad (Environmental Science and Pollution Research, 2023)

Involvement of plant signaling network and cell metabolic homeostasis in nitrogen deficiency-induced early leaf senescence - Muhammad Asad Ullah Asad; Xianyue Guan; Lujian Zhou; Zhao Qian; Zhang Yan; Fangmin Cheng (Plant Science, 2023)

Unraveling the impact of human perturbation on nitrogen cycling in terrestrial ecosystems of lower Himalaya, Pakistan - Tahir Zaman; Saeed Ahmad Asad; Muhammad Irshad; Faridullah; Muhammad Shahzad; Rashid Nazir; Awais Arefeen; Akhtar Iqbal; Farhan Hafeez (Environmental Monitoring and Assessment, 2023)

Dynamic microfluidic-assisted transglutaminase modification of soy protein isolate-chitosan: Effects on structural and functional properties of the adduct and its antioxidant activity after in vitro digestion - Meiyu Gu; Yifan Cui; Asad ur Rehman Muhammad; Mengyue Zhang; Xibo Wang; Lina Sun; Qingshan Chen (Food Research International, 2023)

Simultaneous adsorption of methylene blue and amoxicillin by starch-impregnated MgAl layered double hydroxide: Parametric optimization, isothermal studies and thermo-kinetic analysis - Ghulam Mujtaba; Asad Ullah; Danish Khattak; Mansoor Ul Hassan Shah; Muhammad Daud; Salman Ahmad; Abdul Hai; Faheem Ahmed; Thamraa Alshahrani; Fawzi Banat (Environmental Research, 2023)

Revolutionizing Chronic Obstructive Pulmonary Disease Care with the Open AI Application: ChatGPT - Muhammad Hasnain; Asad Hayat; Akbar Hussain (Annals of Biomedical Engineering, 2023)

Diversity of arthropods in citrus orchards of Sargodha, Pakistan: Use of different trapping techniques - Muhammad Irfan Ullah; Muhammad Arshad; Asad Abdullah; Nimra Altaf; Syed Muhammad Ali Zahid; Muhammad Afzal (International Journal of Tropical Insect Science, 2023)

Co-application of copper oxide nanoparticles and Trichoderma harzianum with physiological, enzymatic and ultrastructural responses for the mitigation of salt stress - Iftikhar Hussain Shah; Irfan Ali Sabir; Asad Rehman; Muhammad Khalid Hameed; Gadah Albashar; Muhammad Aamir Manzoor; Awais Shakoor (Chemosphere, 2023)

RETRACTED: Strigolactone decreases cadmium concentrations by regulating cadmium localization and glyoxalase defense system: Effects on nodules organic acids and soybean yield - Tariq Shah; Muhammad Asad; Zeeshan Khan; Khadija Amjad; Abdulaziz Abdullah Alsahli; Roberto D'amato (Chemosphere, 2023)

Piriformospora indica alter root-associated microbiome structure to enhance Artemisia annua L. tolerance to arsenic - Saeed ur Rahman; Muhammad Khalid; Nan Hui; Asad Rehman; Sadaf-Ilyas Kayani; Xueqing Fu; Han Zheng; Jin Shao; Abid Ali Khan; Mehran Ali; Ayat Taheri; Hang Liu; et al. (Journal of Hazardous Materials, 2023)

Biochar alleviated the toxic effects of PVC microplastic in a soil-plant system by upregulating soil enzyme activities and microbial abundance - Attia Rubab Khalid; Tariq Shah; Muhammad Asad; Ahmad Ali; Eisha Samee; Fazal Adnan; Muhammad Faraz Bhatti; Sven Marhan; Claudia I. Kammann; Ghulam Haider (Environmental Pollution, 2023)

Estimation of in-season nitrogen requirement for drip-irrigated spring maize without or with straw incorporation using critical nitrogen dilution curve - Ru Guo; Rui Qian; Muhammad Asad Naseer; Fei Han; Peng Zhang; Zhikuan Jia; Xiaoli Chen; Xiaolong Ren (Plant and Soil, 2023)

Cold and Drought Stresses in Wheat: A Global Meta-analysis of 21st Century - Irsa Ejaz; Xiaoyu Pu; Muhammad Asad Naseer; Yves N.’Dri Bohoussou; Ying Liu; Muhammad Farooq; Jingting Zhang; Yinghua Zhang; Zhimin Wang; Zhencai Sun (Journal of Plant Growth Regulation, 2023)

Exploring and targeting potential druggable antimicrobial resistance targets ArgS, SecY, and MurA in Staphylococcus sciuri with TCM inhibitors through a subtractive genomics strategy - Aafareen Khan; Saman Sohail; Seerat Yaseen; Sareen Fatima; Ayesha Wisal; Sufyan Ahmed; Mahrukh Nasir; Muhammad Irfan; Asad Karim; Zarrin Basharat; Yasmin Khan; Muhammad Aurongzeb; et al. (Functional & Integrative Genomics, 2023)

The influence of exogenous melatonin and chitosan on secondary metabolites’ production and biological activities of tissue extracts in agitated micro-shoot cultures of Ajuga integrifolia Buch. Ham. ex D.Don - Muhammad Asad Ullah; Faiza Zareen Gul; Gouhar Zaman; Junaid Iqbal; Samantha Drouet; Duangjai Tungmunnithum; Christophe Hano; Bilal Haider Abbasi (Acta Physiologiae Plantarum, 2023)

Prevalence and risk factors of bluetongue in small and large ruminants maintained on Government farms in North-western Pakistan - Muhammad Ishaq; Syed Asad Ali Shah; Nadar Khan; Syed M. Jamal (Research in Veterinary Science, 2023)

Silica quantum dots; an optical nanosensing approach for trace detection of pesticides in environmental and biological samples - Fazila Nazir; Muhammad Asad; Lamia Fatima; Awais Bokhari; Saadat Majeed; Batool Fatima; Abdallah A.A. Mohammed; Rama Rao Karri (Environmental Research, 2023)

Surface water quality, public health, and ecological risks in Bangladesh—a systematic review and meta-analysis over the last two decades - Hazrat Bilal; Xiaowen Li; Muhammad Shahid Iqbal; Yonglin Mu; Roberto Xavier Supe Tulcan; Muhammad Asad Ghufran (Environmental Science and Pollution Research, 2023)

Effects of melatonin and Trichoderma harzianum on pak choi yield, chlorophyll contents and antioxidant defense system under clubroot disease - Shazma Gulzar; Muhammad Aamir Manzoor; Fiza Liaquat; Iftikhar Hussain Shah; Asad Rehman; Muhammad Khalid Hameed; Samiah Arif; Xuanwei Zhou; Yidong Zhang (South African Journal of Botany, 2023)

Distinct climatic regions drive antibiotic resistance genes dynamics across public parks and pristine soil ecosystems - Muhammad Khalid; Xinxin Liu; Bangxiao Zheng; Lantian Su; D. Johan Kotze; Heikki Setälä; Mehran Ali; Asad Rehman; Saeed-ur- Rahman; Nan Hui (Journal of Cleaner Production, 2023)

Seismic risk assessment and hotspots prioritization: a developing country perspective - Rehan Asad; Muhammad Qaiser Saleem; Muhammad Salman Habib; Nadeem Ahmad Mufti; Shaker Mahmood Mayo (Natural Hazards, 2023)

Compressive strength and corrosion behavior of steel bars embedded in concrete produced with ferronickel slag aggregate and fly ash: an experimental study - Rita Irmawaty; Muhammad Akbar Caronge; M. W. Tjaronge; Muhammad Asad Abdurrahman; Syamsul Bahri Ahmad (Innovative Infrastructure Solutions, 2023)

Sublethal effects of spinetoram and emamectin benzoate on key demographic parameters of fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae) under laboratory conditions - Arzlan Abbas; Chen Ri Zhao; Muhammad Arshad; Xiao Han; Ayesha Iftikhar; Faisal Hafeez; Asad Aslam; Farman Ullah (Environmental Science and Pollution Research, 2023)

Temporal study of wastewater surveillance from September 2020 to March 2021: an estimation of COVID-19 patients in Lahore, Pakistan - Muhammad Adnan Ashraf; Muhammad Nawaz; Ali Asif; Muhammad Asad Ali; Adnan Mehmood; Muhammad Waqar Aziz; Muhammad Zubair Shabbir; Nadia Mukhtar; Muhammad Abu Bakr Shabbir; Sohail Raza; Tahir Yaqub (Environmental Science and Pollution Research, 2023)

Subsample stability, change detection and dynamics of oil and metal markets: A recursive approach - Asad Ul Islam Khan; Muhammad Shahbaz; Ayuba Napari (Resources Policy, 2023)

Multibody constrained dynamics of deepwater Y-method installation system - Naeem Ullah; Menglan Duan; Mac Darlington Uche Onuoha; Asad Syed; Muhammad Sajid; Guomin Sun; Wenda Li (Ocean Engineering, 2023)

Mineralogy and PGE geochemistry of chromitites and peridotites of the sapat complex in the indus suture zone, northern Pakistan: implications for magmatic processes in the supra-subduction zone - Zaheen Ullah; Huan Li; Asad Khan; Shah Faisal; Yildirim Dilek; Michael W. Förster; Muhammad Farhan; Umar Ashraf; Salman Ahmed Khattak; Gohar Rehman; Syed Asim Hussain (International Geology Review, 2023)

Evaluating powder preparation of Dodonaea viscosa as a new potential control measure against bacterial wilt of tomato - Kashif Ahmad; Raja Asad Ali Khan; Musharaf Ahmad; Rizwan Khan; Ishrat Naz; Saeed Ullah; Waleed Khan; Muhammad Waleed; Shahab Khan; Asad Zaman (Journal of Plant Pathology, 2023)

Metallic nanoparticles photodegraded antibiotics and co-application improved wheat growth and nutritional quality through stress alleviation - Anum Amin; Maria Manzoor; Muhammad Wajahat Ramay; Ali Hassan; Kiran Hina; Asad Syed; Ali H. Bahkali; Muhammad Arshad (Chemosphere, 2023)

Microplastics alter soil enzyme activities and microbial community structure without negatively affecting plant growth in an agroecosystem - Tariq Shah; Ahmad Ali; Ghulam Haider; Muhammad Asad; Fazal Munsif (Chemosphere, 2023)

Long-term straw incorporation regulates greenhouse gas emissions from biodegradable film farmland, improves ecosystem carbon budget and sustainable maize productivity - Rui Qian; Ru Guo; Muhammad Asad Naseer; Peng Zhang; Xiaoli Chen; Xiaolong Ren (Field Crops Research, 2023)

An Insight into Plant Growth-Promoting Rhizobacteria-Mediated Mitigation of Stresses in Plant - Palakshi Borah; Nirmali Gogoi; Saeed Ahmad Asad; Aparna Jyoti Rabha; Muhammad Farooq (Journal of Plant Growth Regulation, 2023)

Multiple strategies for the development of multienzyme complex for one-pot reactions - Bahzad Ahmad Farhan; Li Zhihe; Shehbaz Ali; Tawaf Ali Shah; Li Zhiyu; Andong Zhang; Sadia Javed; Muhammad Asad (Environmental Science and Pollution Research, 2023)

Fluid source and physicochemical conditions of the polymetallic mineralization in Gawuch Formation, Kohistan Island Arc, NW Pakistan - Muhammad Farhan; Mohammad Arif; Ying Ye; Chun-Feng Li; Xuegang Chen; Dieter Garbe-Schönberg; Tao Wu; Zaheen Ullah; Zahid Hussain; Tehseen Zafar; Izhar Sadiq; Syed Wajid Hanif Bukhari; et al. (Geochemistry, 2023)

A chitosan/fucoidan nanoparticle-loaded pullulan microneedle patch for differential drug release to promote wound healing - Ayesha Younas; Zhuolin Dong; Ziye Hou; Muhammad Asad; Mengru Li; Nan Zhang (Carbohydrate Polymers, 2023)

RETRACTED: Comparative study of ZIF-8-materials for removal of hazardous compounds using physio-chemical remediation techniques - Bazla Sarwar; Asad Ullah Khan; Muhammad Aslam; Awais Bokhari; Muhammad Mubashir; Asma A. Alothman; Mohamed Ouladsmane; Samar A. Aldossari; Wai Siong Chai; Kuan Shiong Khoo (Environmental Research, 2023)

Reconnoitering the capabilities of nodule endophytic Pantoea dispersa for improved nodulation and grain yield of chickpea (Cicer arietinum L.) - Mohsin Tariq; Nayab Hasnain; Ijaz Rasul; Muhammad Azeem Asad; Aqsa Javed; Kamran Rashid; Javeria Shafique; Wajeeha Iram; Amir Hameed; Marriam Zafar (World Journal of Microbiology and Biotechnology, 2023)

Remediation of Environmental Contaminants Through Phytotechnology - Abdul Latif; Aown Abbas; Javed Iqbal; Muhammad Azeem; Waleed Asghar; Rehmat Ullah; Muhammad Bilal; Muhammad Arsalan; Madeeha Khan; Rizwan Latif; Muhammad Ehsan; Asad Abbas; et al. (Water, Air, & Soil Pollution, 2023)

Physiological Mechanisms of Grain Yield Loss Under Combined Drought and Shading Stress at the Post-silking Stage in Maize - Muhammad Asad Naseer; Zhang Nengyan; Irsa Ejaz; Sadam Hussain; Muhammad Ahsan Asghar; Muhammad Farooq; Qian Rui; Abd Ullah; Chen Xiaoli; Ren Xiaolong (Journal of Soil Science and Plant Nutrition, 2023)

Prediction and interpretation of antibiotic-resistance genes occurrence at recreational beaches using machine learning models - Sara Iftikhar; Asad Mustafa Karim; Aoun Murtaza Karim; Mujahid Aizaz Karim; Muhammad Aslam; Fazila Rubab; Sumera Kausar Malik; Jeong Eun Kwon; Imran Hussain; Esam I. Azhar; Se Chan Kang; Muhammad Yasir (Journal of Environmental Management, 2023)

Dual functionalized Ag plasmonic sensor for colorimetric detection of Cr(III)/Hg(II)-carboxyl complexes: Mechanism and its sensing based on the interference of organic ligand - L. Sruthi; Mohammad Asad; Muhammad Nadeem Arshad; Abdullah M. Asiri; S. Sudheer Khan (Journal of Environmental Chemical Engineering, 2023)

Rotation of planting strips and reduction in nitrogen fertilizer application can reduce nitrogen loss and optimize its balance in maize–peanut intercropping - Fei Han; Ru Guo; Sadam Hussain; Shuqing Guo; Tie Cai; Peng Zhang; Zhikuan Jia; Muhammad Asad Naseer; Muhammad Saqib; Xiaoli Chen; Xiaolong Ren (European Journal of Agronomy, 2023)

Prospects of antimicrobial peptides as an alternative to chemical preservatives for food safety - Iqra Kamal; Usman Ali Ashfaq; Sumreen Hayat; Bilal Aslam; Muhammad Hassan Sarfraz; Hamna Yaseen; Muhammad Shahid Riaz Rajoka; Asad Ali Shah; Mohsin Khurshid (Biotechnology Letters, 2023)

Geochemistry and in-situ U-Th/Pb Geochronology of the Jambil Meta-Carbonatites, Northern Pakistan: Implications on Petrogenesis and Tectonic Evolution - Asad Khan; Shah Faisal; Kyle P. Larson; Delores M. Robinson; Huan Li; Zaheen Ullah; Mark Button; Javed Nawab; Muhammad Farhan; Liaqat Ali; Muhammad Ali (Journal of Earth Science, 2023)

Effects of Mirabilis jalapa L. root extract and sildenafil on paroxetine-induced sexual dysfunction in male rats and characterization of its phytoconstituents by UPLC-MS - Asad Ur Rahman; Fiaz Alam; Zia Ur Rehman; Muhammad Khan; Tawseef Ahmad (South African Journal of Botany, 2023)

Nitrogen-rich three-dimensional metal-organic framework microrods as an efficient electrocatalyst for oxygen evolution reaction and supercapacitor applications - Muhammad Imran Anwar; Sumaira Manzoor; Limin Ma; Muhammad Asad; Wenhua Zhang; Zahid Shafiq; Muhammad Naeem Ashiq; Guang Yang (Fuel, 2023)

Salinity mitigates cadmium-induced phytotoxicity in quinoa (Chenopodium quinoa Willd.) by limiting the Cd uptake and improved responses to oxidative stress: implications for phytoremediation - Noman Abdal; Ghulam Abbas; Saeed Ahmad Asad; Ayman A. Ghfar; Ghulam Mustafa Shah; Muhammad Rizwan; Shafaqat Ali; Muhammad Shahbaz (Environmental Geochemistry and Health, 2023)

Contrasting treeline dynamics of pine and birch in response to climate warming in the Karakoram - Munawar Ali; Shalik Ram Sigdel; Xiangyu Zheng; Fayaz Asad; Ru Huang; Haifeng Zhu; Sher Muhammad; Iqtidar Hussain; Saulat Hussain; J. Julio Camarero; Eryuan Liang (Trees, 2022)

Evaluating the safety and efficacy of daprodustat for anemia of chronic kidney disease: a meta-analysis of randomized clinical trials - Kaneez Fatima; Warda Ahmed; Asad Saulat Fatimi; Omar Mahmud; Muhammad Umar Mahar; Ayesha Ali; Syed Roohan Aamir; Muhammad Taha Nasim; Muhammad Bilal Islam; Muhammad Talha Maniya; Dua Azim; Shayan Marsia; et al. (European Journal of Clinical Pharmacology, 2022)

Immunological characterization of chitosan adjuvanted outer membrane proteins of Salmonella enterica serovar Typhi as multi-epitope typhoid vaccine candidate - Ambreen Ayub; Muhammad Usman; Ayesha Ihsan; Quratul Ain; Asad Bashir Awan; Muhammad Wajid; Aamir Ali; Abdul Haque; Mazhar Iqbal; Yasra Sarwar (Molecular Biology Reports, 2022)

Biochar in Combination with Nitrogen Fertilizer is a Technique: To Enhance Physiological and Morphological Traits of Rice (Oryza sativa L.) by Improving Soil Physio-biochemical Properties - Izhar Ali; Quan Zhao; Ke Wu; Saif Ullah; Anas Iqbal; He Liang; Jing Zhang; Ihsan Muhammad; Amanullah; Abdullah Khan; Asad Ali Khan; Ligeng Jiang (Journal of Plant Growth Regulation, 2022)

Circadian Variation in Activities of Blackbuck Under Captivity in Punjab, Pakistan - Zahid Farooq; Muhammad Iqbal; Muhammad Saleem Khan; Sana Asad; Muhammad Wajid (Proceedings of the Zoological Society, 2022)

Genetic characterization of flowering and phytochrome genes in peanut (Arachis hypogaea L.) for early maturity - Sammyia Jannat; Mahmood ul Hassan; Gabriela Toledo Ortiz; Muhammad Kausar Nawaz Shah; Mukhtar Ahmed; Asad Hussain Shah; Abdul Qayyum (Molecular Biology Reports, 2022)

MiRNA fine tuning for crop improvement: using advance computational models and biotechnological tools - Asad Abbas; Adnan Noor Shah; Mohsin Tanveer; Waseem Ahmed; Anis Ali Shah; Sajid Fiaz; Muhammad Mohsin Waqas; Sami Ullah (Molecular Biology Reports, 2022)

Effects of Ferula asafetida, closantel, albendazole, oxfendazole, and ivermectin against Haemonchus contortus in goats and sheep - Abdul Jabbar; Muhammad Zahid Iqbal; Muhammad Ashraf; Aneela Zameer Durrani; Hira Sajjad; Mohammed Nasiru Wana; Asad Ullah; Muhammad Imran; Muhammad Shair Zaman Ghauri; Hafiz Ishfaq Ahmad (Tropical Animal Health and Production, 2022)

Evaluation of insecticidal activity of Beauveria bassiana against different instar larvae of Plutella xylostella by using two different methods of application - Muhammad Shehzad; Muhammad Tariq; Qurban Ali; Asad Aslam; Tariq Mukhtar; Muhammad Faheem Akhtar; Asim Gulzar; Muhammad Faisal (International Journal of Tropical Insect Science, 2022)

Susceptibility of Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) on detached plant parts of transgenic and non-transgenic cotton - Muhammad Jawad Saleem; Faisal Hafeez; Qurban Ali; Asad Aslam; Muhammad Arshad; Dilbar Hussain; Ayesha Iftikhar; Afifa Naeem; Muhammad Saleem (International Journal of Tropical Insect Science, 2022)

Investigating the effect of Aspergillus niger inoculated press mud (biofertilizer) on the potential of enhancing maize (Zea mays. L) yield, potassium use efficiency and potassium agronomic efficiency - Urooj Naeem; Irfan ul Haq; Muhammad Afzaal; Akram Qazi; Abdullah Yasar; Amtul bari Tabinda; Yusra Mahfooz; Asad Ullah Naz; Humera Awan (Cereal Research Communications, 2022)

Genome-wide identification and characterization of a plant-specific Dof transcription factor gene family in olive (Olea europaea) and its comparison with Arabidopsis - Mariyam; Muhammad Shafiq; Muhammad Haseeb; Rana Muhammad Atif; Syed Agha Armaghan Asad Abbas Naqvi; Numan Ali; Muhammad Arshad Javed; Fizza Gillani; Muhammad Saleem Haider (Horticulture, Environment, and Biotechnology, 2021)

Reduction of Errors in Hydrological Drought Monitoring – A Novel Statistical Framework for Spatio-Temporal Assessment of Drought - Zulfiqar Ali; Asad Ellahi; Ijaz Hussain; Amna Nazeer; Sadia Qamar; Guangheng Ni; Muhammad Faisal (Water Resources Management, 2021)

Integration of Seed Priming and Biochar Application Improves Drought Tolerance in Cowpea - Muhammad Farooq; Leila Romdhane; Abdul Rehman; Amal K. M. Al-Alawi; Walid M. Al-Busaidi; Saeed A. Asad; Dong-Jin Lee (Journal of Plant Growth Regulation, 2021)

Comparative efficacy of Ovaprim and hMG (menotropin) to induce breeding in African catfish (Clarias gariepinus) - Muhammad Wajahat Ameer; Farhat Jabeen; Muhammad Asad; Ghazala Kaukab; Amnah Bashir; Misha Rasheed; Hafsa Younis; Naveed Munir; Javaria Nawaz; Rida Zainab; Muhammad Akram (Fish Physiology and Biochemistry, 2021)

An in vitro antiviral activity of iodine complexes against SARS-CoV-2 - Imran Altaf; Muhammad Faisal Nadeem; Nadir Hussain; Muhammad Nawaz; Sohail Raza; Muhammad Abu bakr Shabbir; Muhammad Adnan Ashraf; Muhammad Asad Ali; Sohail Hassan; Muhammad Waqar Aziz; Nazish Matti; Muhammad Ashraf; et al. (Archives of Microbiology, 2021)

Exploring genetic diversity and population structure of Punjab goat breeds using Illumina 50 K SNP bead chip - Raja Danish Muner; Muhammad Moaeen-ud-Din; Ghulam Bilal; Hafiz Muhammad Waheed; Muhammad Sajjad Khan; Muhammad Javaid Asad; Zulfiqar Hussain Kuthu (Tropical Animal Health and Production, 2021)

CO2 separation by supported liquid membranes synthesized with natural deep eutectic solvents - Usman Saeed; Asim Laeeq Khan; Mazhar Amjad Gilani; Muhammad Aslam; Asad Ullah Khan (Environmental Science and Pollution Research, 2021)

Late Cretaceous pelagic laminites at the northwestern margin of Indian plate, Pakistan: implications for basin bathymetry and ophiolite emplacement - Sajjad Ahmad; Suleman Khan; Bilal Wadood; Asad Naseer; Muhammad Noman; Jamal Wadood; Muhammad Muslim (Carbonates and Evaporites, 2021)

Investigating the effect of Aspergillus niger inoculated press mud (biofertilizer) on the potential of enhancing maize (Zea mays L.) yield, phosphorous use efficiency, and phosphorous agronomic efficiency - Urooj Naeem; Muhammad Afzaal; Irfan ul Haq; Akram Qazi; Abdullah Yasar; Amtul Bari Tabinda; Yusra Mahfooz; Asad Ullah Naz; Humera Aslam Awan; Ashfaq Ahmad (Arabian Journal of Geosciences, 2021)

Effects of soil application of two different fipronil formulations on some soil-dwelling non-target arthropods - Muhammad Asad; Sohail Ahmed; Rashad Rasool Khan; Abid Ali; Muhammad Fahad Raza; Ammarah Shabbir; Faisal Munir; Anam Noreen Abbas; Mubashir Tariq (International Journal of Tropical Insect Science, 2021)

Relationship of Nitrogen Deficiency-Induced Leaf Senescence with ROS Generation and ABA Concentration in Rice Flag Leaves - Shamsu Ado Zakari; Muhammad-Asad-Ullah Asad; Zhanyu Han; Qian Zhao; Fangmin Cheng (Journal of Plant Growth Regulation, 2020)

Using GIS tools to detect the land use/land cover changes during forty years in Lodhran District of Pakistan - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Waseem Akram; Hafiz Mohkum Hammad; Mazhar Ali; Nasir Masood; Asad Amin; Hafiz Umar Farid; Syeda Refat Sultana; Shah Fahad; Depeng Wang; et al. (Environmental Science and Pollution Research, 2020)

The impact of airborne pollution and exposure to solar ultraviolet radiation on skin: mechanistic and physiological insight - Atif Ali; Hira Khan; Raheem Bahadar; Asma Riaz; Muhammad Hassham Hassan Bin Asad (Environmental Science and Pollution Research, 2020)

A novel approach for high-level expression and purification of GST-fused highly thermostable Taq DNA polymerase in Escherichia coli - Rahman Ud Din; Muhammad Ismail Khan; Asad Jan; Shah Anwar Khan; Irshad Ali (Archives of Microbiology, 2020)

Spatial modeling of Dengue prevalence and kriging prediction of Dengue outbreak in Khyber Pakhtunkhwa (Pakistan) using presence only data - Hammad Ahmad; Asad Ali; Syeda Hira Fatima; Farrah Zaidi; Muhammad Khisroon; Syed Basit Rasheed; Ihsan Ullah; Saleem Ullah; Muhammad Shakir (Stochastic Environmental Research and Risk Assessment, 2020)

Light-mediated biosynthesis of phenylpropanoid metabolites and antioxidant potential in callus cultures of purple basil (Ocimum basilicum L. var purpurascens) - Munazza Nazir; Muhammad Asad Ullah; Muhammad Younas; Aisha Siddiquah; Muzamil Shah; Nathalie Giglioli-Guivarc’h; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Achromobacter sp. FB-14 harboring ACC deaminase activity augmented rice growth by upregulating the expression of stress-responsive CIPK genes under salinity stress - Muhammad Shahid; Asad Ali Shah; Farwa Basit; Muhammad Noman; Muhammad Zubair; Temoor Ahmed; Tahir Naqqash; Irfan Manzoor; Awais Maqsood (Brazilian Journal of Microbiology, 2020)

First report of cucurbit aphid borne yellows virus (CABYV) infecting melon in Pakistan - Muhammad Ahsan; Muhammad Ashfaq; Tariq Mukhtar; Nadeem Akhtar Abbasi; Zohaib Asad (Journal of Plant Pathology, 2020)

Association of intronic polymorphisms (rs1549339, rs13402242) and mRNA expression variations in PSMD1 gene in arsenic-exposed workers - Saqiba Ahmad; Bushra Arif; Zertashia Akram; Malik Waqar Ahmed; Asad Ullah Khan; Muhammad Zahid Hussain; Faisal Rahman; Mahmood Akhtar Kayani; Ishrat Mahjabeen (Environmental Science and Pollution Research, 2020)

Health risks of heavy metal exposure and microbial contamination through consumption of vegetables irrigated with treated wastewater at Dubai, UAE - Muhammad Iftikhar Hussain; Asad Sarwar Qureshi (Environmental Science and Pollution Research, 2020)

ASTER-based remote sensing investigation of gypsum in the Kohat Plateau, north Pakistan - Asad Khan; Shah Faisal; Muhammad Shafique; Saad Khan; Alam Sher Bacha (Carbonates and Evaporites, 2020)

Nanozymes for medical biotechnology and its potential applications in biosensing and nanotherapeutics - Samman Munir; Asad Ali Shah; Hazir Rahman; Muhammad Bilal; Muhammad Shahid Riaz Rajoka; Abdul Arif Khan; Mohsin Khurshid (Biotechnology Letters, 2020)

Development and Characterization of Bioadhesive Film Embedded with Lignocaine and Calcium Fluoride Nanoparticles - Hira Ghafar; Muhammad Imran Khan; Hafiz Shoaib Sarwar; Samiya Yaqoob; Syed Zajif Hussain; Imran Tariq; Asad Ullah Madni; Gul Shahnaz; Muhammad Farhan Sohail (AAPS PharmSciTech, 2020)

Study of land cover/land use changes using RS and GIS: a case study of Multan district, Pakistan - Sajjad Hussain; Muhammad Mubeen; Waseem Akram; Ashfaq Ahmad; Muhammad Habib-ur-Rahman; Abdul Ghaffar; Asad Amin; Muhammad Awais; Hafiz Umar Farid; Amjad Farooq; Wajid Nasim (Environmental Monitoring and Assessment, 2020)

Comparison of water use efficiency, profitability and consumer preferences of different rice varieties in Punjab, Pakistan - Muhammad Asad ur Rehman Naseer; Muhammad Ashfaq; Amar Razzaq; Qamar Ali (Paddy and Water Environment, 2020)

Anti-pollution cosmetic-based one-step formation of w/o/w multiple emulsion containing D-biotin for skin protection: fabrication and in vitro and in vivo evaluation - Atif Ali; Sajid Iqbal; Aqsa Ilyas; Hira Khan; Muhammad Hassham Hassan Bin Asad; Nighat Fatima; Naveed Akhtar (Drug Delivery and Translational Research, 2019)

Comparative study of the genetic basis of nitrogen use efficiency in wild and cultivated barley - Jawad Munawar Shah; Sidra tul Muntaha; Essa Ali; Azhar Abbas Khan; Syed Hassan Raza Zaidi; Ahmad Naeem Shahzad; Zeshan Hassan; Ahmad Nawaz; Muhammad Rashid; Syed Asad Hussain Bukhari (Physiology and Molecular Biology of Plants, 2019)

Concept Design of the Underwater Manned Seabed Walking Robot - Asghar Khan; Wang Liquan; Wang Gang; Muhammad Imran; Hafiz Muhammad Waqas; Asad A. Zaidi (Journal of Marine Science and Engineering, 2019)
In this paper, a novel concept designed of a multi-legged underwater manned seabed walking robot is presented. The robot will be used in both shallow water current (1–2 m/sec) and deep water up to 500 m. It is powered by an external electric power source through tether cable. It walks on the seabed with six legs, which makes it distinct from conventional screw-propelled underwater robots. It can walk calmly without making the water turbid. Two anterior arms act as manipulators. All leg joints and manipulators are controlled by Brushless Direct Current Motors. Motivation for this concept comes from soldier crab that walk mostly forward and has an egg-shaped body. It is operated by a pilot sitting in a pressurized cabin, and promptly control operations of the robot and manipulator. Preliminary design of the pressurized cabin, using an empirical formula, “ASME PVHO-1 2007” standard, and validation was carried out through ANSYS Workbench. Hydrodynamic forces acting on the robot body and legs are utilized to withstand the water current and external forces to adjust legs and body posture for stability. Buoyancy rules are employed to control its rising and diving motion. All key technologies employed in the development of the robot and their approaching methods are explained. It will provide a safe operation space for humans in underwater operations.

Zinc-lysine prevents chromium-induced morphological, photosynthetic, and oxidative alterations in spinach irrigated with tannery wastewater - Ihsan Elahi Zaheer; Shafaqat Ali; Muhammad Rizwan; Firdaus-e- Bareen; Zohaib Abbas; Syed Asad Hussain Bukhari; Leonard Wijaya; Mohammed Nasser Alyemeni; Parvaiz Ahmad (Environmental Science and Pollution Research, 2019)

Immunoprotective role of LaSota vaccine under immunosuppressive conditions in chicken challenged with velogenic avian avulavirus-1 - Iqra Rauf; Abdul Wajid; Irshad Hussain; Safa Ather; Muhammad Asad Ali (Tropical Animal Health and Production, 2019)

Expression patterns of cp4-epsps gene in diverse transgenic Saccharum officinarum L. genotypes - Muhammad Imran; Andre Luiz Barboza; Shaheen Asad; Zafar M. Khalid; Zahid Mukhtar (Physiology and Molecular Biology of Plants, 2019)

Thermodynamic and kinetic insights into plant-mediated detoxification of lead, cadmium, and chromium from aqueous solutions by chemically modified Salvia moorcroftiana leaves - Syed Muhammad Salman; Asad Ali; Behramand Khan; Mehmood Iqbal; Muhammad Alamzeb (Environmental Science and Pollution Research, 2019)

Assessment of flood-induced changes in soil heavy metal and nutrient status in Rajanpur, Pakistan - Farhan Hafeez; Noman Zafar; Rashid Nazir; Hafiz Muhammad Rashad Javeed; Muhammad Rizwan; Faridullah; Saeed Ahmad Asad; Akhtar Iqbal (Environmental Monitoring and Assessment, 2019)

5-Aminolevulinic Acid-Induced Heavy Metal Stress Tolerance and Underlying Mechanisms in Plants - Shafaqat Ali; Muhammad Rizwan; Abbu Zaid; Muhammad Saleem Arif; Tahira Yasmeen; Afzal Hussain; Muhammad Rizwan Shahid; Syed Asad Hussain Bukhari; Saddam Hussain; Ghulam Hassan Abbasi (Journal of Plant Growth Regulation, 2018)

Redox balance and DNA fragmentation in arsenic-exposed occupational workers from different industries of Pakistan - Maryam Raza; Ishrat Mahjabeen; Muhammad Fahim; Waqar Ahmad Malik; Asad Ullah Khan; Mahmood Akhtar Kayani; Ayesha Khan; Zertashia Akram (Environmental Science and Pollution Research, 2018)

Synthesis of Symmetric Bridged Bis-Pyrazolone Based Metal Complex Acid Dyes and their Applications on Leather - Muhammad Ayaz; Muhammad Ayaz; Farman Ali; Aamer Saeed; Asma Khurshid; Ghulam Shabir; Tanveer Ahmad; Syed Asad Raza Kazmi; Hassan Ali Khan (Journal of Fluorescence, 2018)

Characterization of beet necrotic yellow vein virus in Pakistan - Shawana Ahmad; Asad Ali; Musharaf Ahmad; Najeeb Ullah; Ume Kalsoom Afridi; Nadia Bostan; Rizwana Qureshi; Saleha Tawwab; Ijaz Ahmad; Muhammad Zubair (Journal of Plant Pathology, 2018)

Spatial modeling of rat bites and prediction of rat infestation in Peshawar valley using binomial kriging with logistic regression - Asad Ali; Farrah Zaidi; Syeda Hira Fatima; Muhammad Adnan; Saleem Ullah (Environmental Monitoring and Assessment, 2018)

Rat-bites of an epidemic proportion in Peshawar vale; a GIS based approach in risk assessment - Syeda Hira Fatima; Farrah Zaidi; Muhammad Adnan; Asad Ali; Qaiser Jamal; Muhammad Khisroon (Environmental Monitoring and Assessment, 2018)

Biodegradation of plastics: current scenario and future prospects for environmental safety - Temoor Ahmed; Muhammad Shahid; Farrukh Azeem; Ijaz Rasul; Asad Ali Shah; Muhammad Noman; Amir Hameed; Natasha Manzoor; Irfan Manzoor; Sher Muhammad (Environmental Science and Pollution Research, 2018)

Regional climate assessment of precipitation and temperature in Southern Punjab (Pakistan) using SimCLIM climate model for different temporal scales - Asad Amin; Wajid Nasim; Muhammad Mubeen; Saleem Sarwar; Peter Urich; Ashfaq Ahmad; Aftab Wajid; Tasneem Khaliq; Fahd Rasul; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Hussani Mubarak; et al. (Theoretical and Applied Climatology, 2018)

Radiation efficiency and nitrogen fertilizer impacts on sunflower crop in contrasting environments of Punjab, Pakistan - Wajid Nasim; Ashfaq Ahmad; Asad Amin; Muhammad Tariq; Muhammad Awais; Muhammad Saqib; Khawar Jabran; Ghulam Mustafa Shah; Syeda Refat Sultana; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Muhammad Zaffar Hashmi; et al. (Environmental Science and Pollution Research, 2018)

Citric acid enhanced the antioxidant defense system and chromium uptake by Lemna minor L. grown in hydroponics under Cr stress - Rasham Sallah-Ud-Din; Mujahid Farid; Rashid Saeed; Shafaqat Ali; Muhammad Rizwan; Hafiz Muhammad Tauqeer; Syed Asad Hussain Bukhari (Environmental Science and Pollution Research, 2017)

Phyto-management of Cr-contaminated soils by sunflower hybrids: physiological and biochemical response and metal extractability under Cr stress - Mujahid Farid; Shafaqat Ali; Nudrat Aisha Akram; Muhammad Rizwan; Farhat Abbas; Syed Asad Hussain Bukhari; Rashid Saeed (Environmental Science and Pollution Research, 2017)

Manganese nutrition improves the productivity and grain biofortification of fine grain aromatic rice in conventional and conservation production systems - Aman Ullah; Muhammad Farooq; Asif Nadeem; Abdul Rehman; Saeed A. Asad; Ahmad Nawaz (Paddy and Water Environment, 2017)

Are Karakoram temperatures out of phase compared to hemispheric trends? - Fayaz Asad; Haifeng Zhu; Hui Zhang; Eryuan Liang; Sher Muhammad; Suhaib Bin Farhan; Iqtidar Hussain; Muhammad Atif Wazir; Moinuddin Ahmed; Jan Esper (Climate Dynamics, 2017)

Genetically transformed tobacco plants expressing synthetic EPSPS gene confer tolerance against glyphosate herbicide - Muhammad Imran; Shaheen Asad; Andre Luiz Barboza; Esteban Galeano; Helaine Carrer; Zahid Mukhtar (Physiology and Molecular Biology of Plants, 2017)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Production of α-1,4-glucosidase from Bacillus licheniformis KIBGE-IB4 by utilizing sweet potato peel - Muhammad Asif Nawaz; Zainab Bibi; Asad Karim; Haneef Ur Rehman; Muhsin Jamal; Tour Jan; Afsheen Aman; Shah Ali Ul Qader (Environmental Science and Pollution Research, 2017)

Tourism in Austria: biodiversity, environmental sustainability, and growth issues - Muhammad Asad Saleem Malik; Syed Asim Shah; Khalid Zaman (Environmental Science and Pollution Research, 2016)

What do we really know about alien plant invasion? A review of the invasion mechanism of one of the world’s worst weeds - Ali Ahsan Bajwa; Bhagirath Singh Chauhan; Muhammad Farooq; Asad Shabbir; Steve William Adkins (Planta, 2016)

Anthocyanin production in the hyperaccumulator plant Noccaea caerulescens in response to herbivory and zinc stress - Saeed Ahmad Asad; Said Muhammad; Muhammad Farooq; Aftab Afzal; Martin Broadley; Scott Young; Helen West (Acta Physiologiae Plantarum, 2015)

Development of broad-spectrum insect-resistant tobacco by expression of synthetic cry1Ac and cry2Ab genes - Muhammad Nouman Sohail; Sohail Mehmood Karimi; Shaheen Asad; Shahid Mansoor; Yusuf Zafar; Zahid Mukhtar (Biotechnology Letters, 2012)

Partial resistance to powdery mildew in German spring wheat ‘Naxos’ is based on multiple genes with stable effects in diverse environments - Qiongxian Lu; Åsmund Bjørnstad; Yan Ren; Muhammad Azeem Asad; Xianchun Xia; Xinmin Chen; Fang Ji; Jianrong Shi; Morten Lillemo (Theoretical and Applied Genetics, 2012)

Antihaemorrhagic potentials of Fagonia cretica against Naja naja karachiensis (black Pakistan cobra) venom - Muhammad Tahir Razi; Muhammad Hassham Hassan Bin Asad; Taous Khan; Muhammad Zabta Chaudhary; Muhammad Tayyab Ansari; Muhammad Anwar Arshad; Qazi Najam-us Saqib (Natural Product Research, 2011)

Erratum to: Engineering cotton (Gossypium hirsutum L.) for resistance to cotton leaf curl disease using viral truncated AC1 DNA sequences - Jamil A. Hashmi; Yusuf Zafar; Muhammad Arshad; Shahid Mansoor; Shaheen Asad (Virus Genes, 2011)

Engineering cotton (Gossypium hirsutum L.) for resistance to cotton leaf curl disease using viral truncated AC1 DNA sequences - Jamil A. Hashmi; Yusuf Zafar; Muhammad Arshad; Shahid Mansoor; Shaheen Asad (Virus Genes, 2011)

Comparative efficacy of surface drying and re-drying seed priming in rice: changes in emergence, seedling growth and associated metabolic events - Muhammad Farooq; Abdul Wahid; Nazir Ahmad; Saeed A. Asad (Paddy and Water Environment, 2010)

Microemulsion System with Improved Loading of Piroxicam: A Study of Microstructure - Muhammad Faizan Nazar; Asad Muhammad Khan; Syed Sakhawat Shah (AAPS PharmSciTech, 2009)

Comparison of conventional puddling and dry tillage in rice–wheat system - Muhammad Farooq; Shahzad M. A. Basra; Saeed A. Asad (Paddy and Water Environment, 2008)

Decolorization potential of mixed microbial consortia for reactive and disperse textile dyestuffs - Muhammad Asgher; H. N. Bhatti; S. A. H. Shah; M. Javaid Asad; R. L. Legge (Biodegradation, 2007)

Hyperactivation and thermostabilization of Phanerochaete chrysosporium lignin peroxidase by immobilization in xerogels - Muhammad Asgher; M. Javaid Asad; Haq Nawaz Bhatti; Raymond L. Legge (World Journal of Microbiology and Biotechnology, 2007)